Fiber treatment agent composition, fiber processed product, and method for producing fiber processed product
By using sulfate polysaccharides in the fiber treatment agent combination and adopting a specific treatment method, the problem of difficulty in effectively attaching polysaccharide derivatives to non-silk fibers in the prior art is solved, and the multifunctional performance of the fiber is improved and the performance durability of the fiber is achieved.
Patent Information
- Application Number
- JP2023171919
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-03
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to effectively mix and attach polysaccharide derivatives from Swissinari on non-silk fibers such as cotton, linen, and synthetic fibers, making it difficult for these fibers to obtain good water absorption, moisturizing and rapid drying functions.
The fiber treatment agent is combined with polysaccharides containing sulfate, and after mixing with water and stirring, it is processed using a specific equipment such as a Sany electric stirrer or a grinder to ensure that the fiber treatment agent is evenly attached to the fiber surface.
The uniform adhesion of fiber treatment agent on various fibers is achieved, and the water absorption, moisturizing, rapid drying, anti-fouling and anti-static properties of the fiber are improved, and these properties are still maintained after washing.
Smart Images

Figure 2025062719000001 
Figure 2025062719000002 
Figure 2025062719000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a fiber treatment composition, a processed fiber product, and a method for producing the processed fiber product. [Background technology]
[0002] In recent years, in order to impart functionality such as moisture retention to fibers, various functional agents have been attached to the fiber surface or incorporated into the fiber. For example, Patent Document 1 proposes a rayon fiber containing Aphanothece sacrum-derived polysaccharides in a ratio of 0.01 to 0.5 parts by mass per 100 parts by mass of rayon in order to obtain a rayon fiber with excellent moisture absorption, water absorption, and quick-drying properties. It is reported that a rayon fiber with excellent moisture absorption, water absorption, and quick-drying properties can be obtained. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-11542 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, Patent Document 1 describes that Aphanothece sacrum-derived polysaccharides are dissolved in a fiber raw material solution of rayon and then spun. Since the fiber treatment agent is also contained inside the fiber, there is a problem in maintaining the original properties of the fiber while imparting new properties such as moisture absorption. In addition, it is difficult to mix Aphanothece sacrum-derived polysaccharides into the raw material solution of various fibers or the fibers themselves for plant fibers, animal fibers, and synthetic fibers other than rayon, and there is a problem in applying it to fibers other than rayon.
[0005] The present invention has been made to solve the above problems, and aims to provide a fiber treatment composition containing a sulfated polysaccharide, which can be used to obtain a fiber processed product that is excellent in water absorption, moisture retention, moisture absorption and release properties, and has a pleasant texture. Another aim is to provide a fiber treatment composition that can obtain a fiber processed product that is imparted with antifouling and antistatic properties in addition to the above properties. Another aim is to provide a fiber processed product that is imparted with washing resistance that does not lose its functionality even after washing in addition to the above properties. Another aim is to provide a fiber processed product obtained using the fiber treatment composition, and a method for producing the fiber processed product. [Means for solving the problem]
[0006] The present disclosure includes the following embodiments [1] to
[13] . [1] A fiber treatment composition comprising a fiber treatment agent and water, The fiber treatment agent contains a sulfated polysaccharide, The fiber treatment composition, wherein the content of the sulfated polysaccharide in the fiber treatment composition is 0.001 to 5% by mass. [2] The fiber treatment composition according to [1], wherein the sulfated polysaccharide is derived from algae. [3] The fiber treatment composition according to [1] or [2], further comprising a binder. [4] The fiber treatment agent further contains water and is a dispersible fiber treatment agent obtained by a dispersion treatment, The fiber treatment agent composition according to any one of [1] to [3], wherein the dispersible fiber treatment agent has a viscosity change rate (%) of 20% or more before and after dispersion treatment, as represented by the following formula (1): [(AB) / A]×100……(1) (In formula (1), A is the viscosity (milliPascal seconds (mPa s)) of the fiber treatment agent before dispersion treatment, and B is the viscosity (milliPascal seconds (mPa s)) of the dispersible fiber treatment agent after dispersion treatment.) [5] The fiber treatment composition according to [4], wherein the content of the sulfated polysaccharide is 3.0% or less based on the total mass of the dispersible fiber treatment agent. [6] A step of mixing at least a sulfated polysaccharide and water and stirring the resulting mixed composition with a stirrer; A step of dispersing the stirred mixed composition using a disperser to obtain a dispersible fiber treatment agent; preparing a fiber treatment composition using the dispersible fiber treatment agent; A method for producing a fiber treatment composition comprising the steps of: [7] A method for producing the fiber treatment composition according to any one of [4] to [5], mixing the sulfated polysaccharide with water and stirring the resulting mixed composition with a stirrer; A step of dispersing the stirred mixed composition using a disperser to obtain the dispersible fiber treatment agent; preparing a fiber treatment composition using the dispersible fiber treatment agent; A method for producing a fiber treatment composition comprising the steps of: [8] The method for producing a fiber treatment composition according to [6] or [7], wherein the stirrer is at least one selected from the group consisting of a homodisper, an emulsifier, a line mixer, a three-one motor, and a magnetic stirrer. [9] The method for producing a fiber treatment composition according to any one of [6] to [8], wherein the dispersing machine is at least one selected from the group consisting of a sand mill, a bead mill, a pebble mill, a ball mill, a pearl mill, a basket mill, an attritor, a Dyno Mill, a bore mill, a Viscomill, a motor mill, an SC mill, a drys mill, a paint conditioner, an ultrasonic dispersing machine (ultrasonic homogenizer), a high-pressure homogenizer, a Nanomizer, an Ultimizer, a roll mill, a Henschel mixer, a pressure kneader, an intensive mixer, a Banbury mixer, and a planetary mixer.
[10] A textile processed product comprising a textile substrate and a textile treatment agent adhered to the textile substrate, The fiber treatment agent is contained in the fiber treatment agent composition according to any one of [1] to [5], The fiber base material does not contain rayon, The processed fiber product, wherein the amount of the sulfated polysaccharide attached to the fiber base material is 0.003 to 20.0 parts by mass per 100 parts by mass of the fiber base material.
[11] A method for producing a textile product, comprising a step of treating a textile substrate with the fiber treatment composition according to any one of [1] to [5] to obtain a textile product, A method for producing a textile product, comprising: an application step of applying the fiber treatment composition to the textile substrate; and a drying step of removing water from the textile substrate to which the fiber treatment composition has been applied.
[12] A method for producing a textile product, comprising a step of treating a textile substrate with the fiber treatment composition according to any one of [1] to [5] to obtain a textile product, The manufacturing method includes a step of applying the fiber treatment composition to the fiber substrate, and a step of drying the fiber substrate to remove water from the fiber substrate to which the fiber treatment composition has been applied, A method for producing a textile product, characterized in that the method is at least one selected from the group consisting of the following (I) to (III): (I) before the adhesion step, a step of pretreating a fiber substrate with a fiber pretreatment composition containing a cationic resin to obtain a pretreated fiber substrate, The applying step is a step of applying the fiber treatment composition to the pre-treated fiber substrate. (II) The fiber treatment composition further contains a crosslinking agent, and the drying step includes a heat treatment step at a temperature in the range of 80°C to 260°C. (III) The drying step includes a heat treatment step using high-temperature steam in the temperature range of 120° C. or higher.
[13] A textile product manufactured using the method for manufacturing a textile product according to
[12] , The processed fiber product, wherein the amount of the sulfated polysaccharide attached to the fiber base material is 0.003 to 20.0 parts by mass per 100 parts by mass of the fiber base material. Effect of the Invention
[0007] According to the present invention, it is possible to provide a fiber treatment composition, a fiber processed product, and a method for producing the fiber processed product, which are excellent in water absorption, moisture retention, moisture absorption and release properties, and which can provide a fiber processed product that is pleasant to the touch. It is also possible to provide a fiber treatment composition, a fiber processed product, and a method for producing the fiber processed product, which can provide a fiber processed product imparted with stain resistance and antistatic properties. Furthermore, it is also possible to provide a fiber processed product imparted with washing resistance that does not lose functionality even after washing, and a method for producing the fiber processed product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present invention will be described in more detail below. Note that the present invention is not limited to the following embodiments.
[0009] "~" means greater than or equal to the value before the "~", and less than or equal to the value after the "~".
[0010] (Fiber treatment composition) The fiber treatment composition of the present embodiment includes a fiber treatment agent and water. The fiber treatment agent includes a sulfated polysaccharide. The content of the sulfated polysaccharide in the fiber treatment composition is 0.001 to 50.0 mass%, preferably 0.002 to 20.0 mass%, more preferably 0.003 to 10.0 mass%, even more preferably 0.01 to 5.0 mass%, particularly preferably 0.02 to 3.0 mass%, and most preferably 0.03 to 1.0 mass%. In addition, a binder and other additives may be included as necessary. When a binder is included, the content of the binder in the fiber treatment composition is preferably 0.1 to 30 mass%, more preferably 0.5 to 20 mass%, and even more preferably 1 to 10 mass%. When the content of the binder in the fiber treatment composition is 0.5% by mass or more, the sulfated polysaccharide can be sufficiently fixed to the fiber via the binder, which is particularly preferred, and when it is 20% by mass or less, the functionality of the sulfated polysaccharide, such as water absorption, moisture retention, moisture absorption and release, soil resistance, and antistatic properties, and washing resistance, are not hindered, which is particularly preferred. The content of the binder in the fiber treatment composition is preferably 0.5 to 100 parts by mass, more preferably 1 to 50 parts by mass, and even more preferably 3 to 30 parts by mass, relative to 100 parts by mass of the sulfated polysaccharide. When the content of the binder is 1 part by mass or more relative to 100 parts by mass of the sulfated polysaccharide, the sulfated polysaccharide can be sufficiently fixed to the fiber via the binder, which is preferred, and when it is 50 parts by mass or less, the functionality of the sulfated polysaccharide fixed via the binder can be exhibited, which is preferred.
[0011] [Textile treatment agent] The fiber treatment agent according to this embodiment is a fiber treatment composition that is applied to the fiber substrate, and then a drying process is performed to remove water from the applied fiber treatment composition, and the fiber treatment agent is then applied to the surface of the fiber substrate. The fiber treatment agent according to this embodiment contains a sulfated polysaccharide. In addition to the sulfated polysaccharide, the fiber treatment agent may contain a binder and may further contain other additives. It may or may not contain water. Note that "other additives" has the same meaning as "other additives" described above in (Fiber treatment agent composition).
[0012] <Sulfated polysaccharide> Sulfated polysaccharides are a type of compound called a "sugar chain" in which saccharides such as glucose are bonded in long chains, and are a general term for polysaccharides that have been chemically modified with sulfate groups. Examples of sulfated polysaccharides according to the present embodiment include those that exist naturally and those to which sulfate groups have been artificially added. The weight-average molecular weight of the sulfated polysaccharide according to this embodiment is not particularly limited as long as the effects of the present invention can be obtained, but is preferably 500,000 to 30 million, more preferably 1,000,000 to 25,000,000 in terms of durability after fixing to fibers, and even more preferably 2,000,000 to 20,000,000 in terms of suitable dispersion stability as the fiber treatment composition of the present invention.
[0013] Examples of sulfated polysaccharides in this embodiment include the group consisting of chondroitin sulfate, dermatan sulfate, and salts thereof; the group consisting of polysaccharides having sulfate groups in part of known polysaccharides composed of D-glucosamine, D-galactosamine, D-glucuronic acid, L-iduronic acid, D-galacturonic acid, D-glucose, D-galactose, D-xylose, etc., and salts thereof; and sulfated polysaccharides of natural origin. Of these, sulfated polysaccharides of natural origin are preferred. The naturally occurring sulfated polysaccharides are preferably, for example, sulfated polysaccharides originating from algae, such as at least one sulfated polysaccharide derived from macroalgae, microalgae, or cyanobacteria (blue-green algae), or a mixture of sulfated polysaccharides derived from macroalgae, microalgae, or cyanobacteria. For example, at least one type of sulfated polysaccharide selected from the following polysaccharides originating from algae can be mentioned.
[0014] red macroalgae selected from among the agar-, carrageenan-, porphyrin-, furan-, or complex sulfated galactan-producing Rhodophyceae of the genera Gracilaria, Halymenia, Gelidium, Pterocladia, Acanthopeltis, Campylaephora, Ceranium, Eucheuma, Chondrus, Porphyra, Laurencia, Furcellaria, Gloiopeltis, and Iridea; green macroalgae selected from the Chlorophyceae family of the genus Ulva that produce polysaccharides, such as ulvan; A brown macroalgae selected from the Pheophyceae family of the genus Fucus, Aschophyllum or Cladosiphon that produces sulfated furans. A cyanobacteria such as Aphanothece sacrum. Among the above sulfated polysaccharides originating from algae, sulfated polysaccharides derived from A. suizenjimino are preferred. A. suizenjimino is a type of cyanobacteria that belongs to the Chroococcales and has photosynthetic ability. A. suizenjimino is a freshwater cyanobacteria that grows naturally in a specific area of Kyushu and forms a colony with a flat shape made up of multiple cells. The outer surface of the colony is covered with a gel-like secretion formed from polysaccharides and the like, and the colony grows to a diameter of about 50 mm.
[0015] The sulfated polysaccharide according to this embodiment can be at least one sulfated polysaccharide obtained by chemically modifying a known polysaccharide.
[0016] The sulfated polysaccharide of this embodiment is derived from the freshwater cyanobacterium Aphanothece sacrum, has an average molecular weight of 2,000,000 or more, and has a repeating structure of glycan units in which glycan structures having hexose structures and glycan structures having pentose structures are linked in a linear or branched chain manner via α-glycosidic bonds or β-glycosidic bonds, and in the glycan units, 2.7 or more hydroxyl groups per 100 hydroxyl groups are sulfated or the sulfur element accounts for 1.5% by weight or more of the total elements, and it is preferable that the glycan units are glycan derivatives that contain lactated sulfated saccharides as glycan structures. The provision "derived from Aphanothece saccharum" is part of the provision for identifying the sugar derivative as a substance, and does not limit the source of the sugar derivative or the method of production. The sulfated saccharide is preferably at least one selected from sulfated muramic acid and sulfated N-acetylmuramic acid. The sugar derivatives include at least glucose, galactose, and mannose shown in chemical formula (a), galactosamine shown in chemical formula (b), xylose and arabinose shown in chemical formula (c), glucuronic acid and galacturonic acid shown in chemical formula (d), and fucose and rhamnose shown in chemical formula (e), and have functional groups selected from a group of functional groups including at least a sulfate group, a lactic acid group, and a methyl group bonded to any bonding position in these sugar structures.
[0017] [ka]
[0018] [ka]
[0019] [ka]
[0020] [ka]
[0021] [ka]
[0022] The sugar derivative is derived from the freshwater cyanobacterium Aphanothece sacrum, has an average molecular weight of 2,000,000 or more, and contains at least a trisaccharide structure having the sequence shown in the following chemical formula (f) and all of the disaccharide structures having the sequences listed in the following (i) to (vi).
[0023] [ka]
[0024] (Chemical formula (f) shows a trisaccharide structure of hexose, hexose, and N-acetylmuramic acid, R i , R ii represents a sugar. Any -OH in formula (f) is -OSO3 - Or -OCH3.) (i) A disaccharide structure consisting of a hexose and a pentose, which is either xylose or arabinose. (ii) A disaccharide structure consisting of a hexose and a deoxyhexose which is either fucose or rhamnose. (iii) A pentose-pentose disaccharide structure. (iv) A disaccharide structure consisting of a pentose and a deoxyhexose. (v) Disaccharide structure of hexosamine and hexinsamine. (vi) A disaccharide structure consisting of a uronic acid, which is glucuronic acid or galacturonic acid, and a deoxyhexose.
[0025] The average molecular weight of the sugar derivative may be 20,000,000 or more. The molar ratio of the main sugar structures constituting the sugar derivative may be arabinose 1.1:fucose 3.7:rhamnose 15.4:xylose 17.0:mannose 10.5:galactose 12.3:galacturonic acid 4.6:glucuronic acid 4.7:glucose 28.8:galactosamine 2.03.
[0026] The sugar derivative may be extracted from the freshwater cyanobacterium Aphanothece sacrum as a raw material to obtain a crude sugar derivative, which may be used as is, or may be further purified as necessary before use.
[0027] The sulfated polysaccharide according to the present embodiment is preferably a polysaccharide containing at least monosaccharides such as (i) 6-deoxy sugar (and / or pentose), (ii) uronic acid, (iii) hexapyranose, and (iv) sulfated muramic acid as structural units. In the sulfated polysaccharide having structural units derived from the monosaccharides, the sequence of the structural units is not particularly limited, and may be, for example, in the order of (i), (ii), (iii), and (iv). The sulfated polysaccharide according to the present embodiment is particularly preferably a sulfated polysaccharide represented by the following formula (1). Note that the sequence of structural units (monosaccharides) represented by formula (1) is an example, and the sequence of the structural units is not limited to the sequence of general formula (1).
[0028] [ka]
[0029] The proportion and average molecular weight of monosaccharides constituting the sulfated polysaccharide having the constituent units derived from the monosaccharides (i) to (iv) above are not particularly limited. For example, the proportion of sulfated muramic acid in the total constituent units of the sulfated polysaccharide may be in the range of 0.1 to 20 mol %, and the proportion of uronic acid in the total constituent units may be in the range of 1 to 50 mol %. The sulfated polysaccharide may have a sulfate group content of 1 to 50 mol % per sugar residue, preferably a sulfate group content of 5 to 25 mol %. The sulfated polysaccharide may have a carboxylic acid content of 5 to 80 mol % per sugar residue, preferably a carboxylic acid content of 10 to 50 mol %. The number of types of constituent saccharides of the sulfated polysaccharide may be 3 or more, and preferably 5 or more. The weight-average molecular weight of the sulfated polysaccharide is not particularly limited as long as the effects of the present invention can be obtained, but is 500,000 to 30 million, preferably 1 million to 25 million from the viewpoint of durability after fixing to fibers, and more preferably 2 million to 20 million from the viewpoint of suitable dispersion stability as the fiber treatment composition of the present invention.
[0030] "Sakuran" An example of a sulfated polysaccharide derived from A. sacrum is "Sacrum (registered trademark)". Sacrum, which is one type of sulfated polysaccharide according to this embodiment, is a polysaccharide extracted from A. sacrum, which is a species endemic to Japan. Although Sacrum according to this embodiment is not limited to that derived from A. sacrum, it is preferable that it is a sulfated polysaccharide derived from A. sacrum. SACRAN (registered trademark; hereinafter, the word "registered trademark" may be omitted) according to this embodiment is a polymer containing the same structural units as the polymer extracted from Aphanothece sacrum. For example, it may be a sulfated polysaccharide containing monosaccharides such as 6-deoxy sugar (and / or pentose), uronic acid, hexapyranose, and sulfated muramic acid as structural units. A preferred example of such a sacran is a sulfated polysaccharide extracted from Aphanothece sacrum (hereinafter, sometimes referred to as "sacran"). An example of a method for extracting sacran from Aphanothece sacrum is described in International Publication WO2008 / 062574.
[0031] For example, a specific method for extracting sacran from A. sacrum is to freeze and wash an appropriate amount of A. sacrum with water to remove water-soluble pigments, then remove fat-soluble pigments with an organic solvent such as ethanol, and dry the algae of A. sacrum. Then, 0.1N sodium hydroxide is added to the dried algae of A. sacrum, and the mixture is stirred at 60 to 80°C for 6 hours. The sugar derivative solution obtained by the above operation is neutralized, filtered, concentrated, and dried. In another example, sacran can be extracted from A. sacrum by heating an aqueous dispersion of A. sacrum in an autoclave at 135°C for 30 minutes. The extracted sacran may be purified by centrifugation, filtration, alcohol washing, etc. In addition, before extracting sacran from A. sacrum, A. sacrum may be frozen and then thawed, and then a process of removing pigments may be performed. SACRAN according to this embodiment is a polysaccharide containing monosaccharides such as (A): 6-deoxy sugar (and / or pentose), (B): uronic acid, (C): uronic acid, (D): hexapyranose, and (F): sulfated muramic acid as structural units. An example of the state in which they are linked is shown in the following formula (1). Note that the sequence of structural units (monosaccharides) shown in formula (2) is only an example, and the sequence of structural units is not limited to the sequence of general formula (2).
[0032] [ka]
[0033] In this embodiment, the ratio and average molecular weight of monosaccharides constituting SACRAN vary depending on the harvesting time and place of Aphanothece sacran. In one example of SACRAN, the ratio of sulfated muramic acid to all structural units is in the range of 0.1 to 20 mol%, and the ratio of uronic acid to all structural units is in the range of 1 to 50 mol%. Moreover, the weight-average molecular weight of SACRAN, for example, is in the range of 1 million to 30 million.
[0034] A specific example of SACRAN in this embodiment is SACRAN manufactured by Green Science Materials Co., Ltd.
[0035] <Binder> The binder according to the present embodiment functions as a binder for the fibers, and is preferably a compound that mixes with water or an aqueous dispersion that is stably dispersed in water. The binder preferably has an anionic or cationic ionic group in order to increase the affinity between the fibers and the sulfated polysaccharide. Examples of the binder include urethane resin, acrylic resin, butadiene polymer, ethylene-vinyl acetate copolymer, natural rubber, silicone resin, and polyester resin. The binder may be in the form of an emulsion, dispersion, powder, or the like. Examples of the binder include an acrylic resin aqueous dispersion, a urethane resin aqueous dispersion, a butadiene polymer aqueous dispersion, an ethylene-vinyl acetate copolymer aqueous dispersion, a natural rubber latex, a polyester resin aqueous dispersion, and a silicone resin aqueous dispersion. To introduce an ionic group into these binders, a unit derived from a monomer having an ionic group can be copolymerized. Examples of the ionic group include anionic groups having acidic groups such as carboxyl groups, sulfonic acid groups, and phosphoric acid groups, or groups partially or entirely neutralized with bases such as metal hydroxides such as potassium hydroxide and sodium hydroxide, and organic substances such as ammonia and triethylamine; cationic groups having basic groups such as amino groups, or groups partially neutralized with inorganic acids or organic acids. In addition to the above dispersions, cationic resins having polyallylamine or quaternary ammonium salt / pyridinium salt structures can also be used as binders. These binders can be used alone or in combination of two or more. Among these, acrylic resin water dispersions and / or urethane resin water dispersions can be used because they provide even better texture and water absorbency of the fiber processed products described below.
[0036] Furthermore, the binder according to the present embodiment may contain various resin compositions as binders, such as other resin emulsions, solution resins, epoxy resins, and urethane resins, within the scope of not impairing the effects of the present invention.
[0037] Examples of the binder according to the present embodiment include acrylic resins, urethane resins, polyester resins, silicone resins, cationic resins, etc. Examples of these resins are shown below.
[0038] "Acrylic resin"
[0039] The acrylic resin water dispersion is, for example, a polymerizable monomer having an acrylic monomer as an essential component, polymerized. In order to improve the solubility or dispersion in water described later, it is preferable to use a polymerizable monomer having a carboxyl group.
[0040] Examples of the acrylic monomer used as a raw material for the acrylic resin aqueous dispersion include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate (laurate), and the like. alkyl (meth)acrylates such as ethyl (meth)acrylate, tridecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate (stearyl (meth)acrylate), nonadecyl (meth)acrylate, and icosanyl (meth)acrylate; aromatic (meth)acrylates such as benzyl (meth)acrylate and phenylethyl (meth)acrylate; cyclohexyl (meth)acrylate, isoboronic acid, (Meth)acrylates having an alicyclic structure such as aryl (meth)acrylate; alkyl group-terminated polyalkylene glycol mono(meth)acrylates such as methoxy polyethylene glycol mono(meth)acrylate, methoxy polypropylene glycol mono(meth)acrylate, octoxy polyethylene glycol mono(meth)acrylate, octoxy polypropylene glycol mono(meth)acrylate, lauroxy polyethylene glycol mono(meth)acrylate, lauroxy polypropylene glycol mono(meth)acrylate, stearoxy polyethylene glycol mono(meth)acrylate, stearoxy polypropylene glycol mono(meth)acrylate, allyloxy polyethylene glycol mono(meth)acrylate, allyloxy polypropylene glycol mono(meth)acrylate, nonylphenoxy polyethylene glycol mono(meth)acrylate, and nonylphenoxy polypropylene glycol mono(meth)acrylate; silane-based (meth)acrylates such as trimethylsiloxyethyl (meth)acrylate;(Meth)acryloyloxyalkylsilane compounds such as 3-(meth)acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxypropylmethyldimethoxysilane, 3-(meth)acryloyloxypropyltriethoxysilane, and 3-(meth)acryloyloxypropylmethyldiethoxysilane; fluorine-based (meth)acrylates such as perfluoroalkylethyl (meth)acrylate; glycidyl (meth)acrylate, epoxy (meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylene glycol Examples of (meth)acrylate compounds include ricol tetra(meth)acrylate, 2-hydroxy-1,3-diacryloxypropane, 2,2-bis[4-(acryloxymethoxy)phenyl]propane, 2,2-bis[4-(acryloxyethoxy)phenyl]propane, dicyclopentenyl(meth)acrylate, tricyclodecanyl(meth)acrylate, tris(acryloxyethyl)isocyanurate, and urethane(meth)acrylate; and (meth)acrylates having an alkylamino group such as dimethylaminoethyl(meth)acrylate, diethylaminoethyl(meth)acrylate, and dimethylaminopropyl(meth)acrylate. These (meth)acrylate compounds (c) may be used alone or in combination of two or more.;
[0041] In the present invention, "(meth)acrylate" refers to either or both of methacrylate and acrylate, "(meth)acryloyl" refers to either or both of methacryloyl and acryloyl, and "(meth)acrylic acid" refers to either or both of methacrylic acid and acrylic acid.
[0042] In addition, when a carboxyl group is introduced into the acrylic resin aqueous dispersion, for example, a polymerizable monomer having a carboxyl group, such as (meth)acrylic acid, itaconic acid, crotonic acid, fumaric acid, maleic acid, maleic anhydride, citraconic acid, etc., can be used as a raw material. These polymerizable monomers may be used alone or in combination of two or more. After a carboxyl group is introduced into the acrylic resin aqueous dispersion using these polymerizable monomers having a carboxyl group, a part or all of the carboxyl group may be neutralized with a base such as a metal hydroxide, such as potassium hydroxide, sodium hydroxide, etc., or an organic substance, such as ammonia, triethylamine, etc.
[0043] The acrylic resin water dispersion can be produced, for example, by a known emulsion polymerization method.
[0044] "Urethane resin" The urethane resin water dispersion is one in which the urethane resin can be dispersed in water or an aqueous medium, and examples of the water dispersion that can be used include an aqueous urethane resin having a hydrophilic group such as an anionic group, a cationic group, or a nonionic group; an aqueous urethane resin forcibly dispersed in an aqueous medium with an emulsifier, etc. These water dispersions of urethane resin may be used alone or in combination of two or more kinds.
[0045] The aqueous urethane resin having an anionic group can be obtained, for example, by using, as a raw material, one or more compounds selected from the group consisting of compounds having a carboxyl group and compounds having a sulfonyl group.
[0046] Examples of the compound having a carboxyl group that can be used include 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, 2,2-dimethylolbutyric acid, 2,2-dimethylolpropionic acid, 2,2-valeric acid, etc. These compounds may be used alone or in combination of two or more.
[0047] Examples of the compound having a sulfonyl group that can be used include 3,4-diaminobutanesulfonic acid, 3,6-diamino-2-toluenesulfonic acid, 2,6-diaminobenzenesulfonic acid, N-(2-aminoethyl)-2-aminoethylsulfonic acid, etc. These compounds may be used alone or in combination of two or more.
[0048] The carboxyl group and sulfonyl group may be partially or completely neutralized with a basic compound in the aqueous urethane resin composition. Examples of the basic compound include organic amines such as ammonia, triethylamine, pyridine, and morpholine; alkanolamines such as monoethanolamine and dimethylethanolamine; and metal base compounds including sodium, potassium, lithium, and calcium.
[0049] The aqueous urethane resin having a cationic group can be obtained, for example, by using one or more compounds having an amino group as raw materials.
[0050] Examples of the compound having an amino group include compounds having primary and secondary amino groups such as triethylenetetramine and diethylenetriamine, compounds having a tertiary amino group such as N-alkyldialkanolamines such as N-methyldiethanolamine and N-ethyldiethanolamine, and N-alkyldiaminoalkylamines such as N-methyldiaminoethylamine and N-ethyldiaminoethylamine, etc. These compounds may be used alone or in combination of two or more.
[0051] The method for obtaining the aqueous urethane resin having a nonionic group may, for example, be a method using one or more compounds having an oxyethylene structure as a raw material.
[0052] Examples of the compound having an oxyethylene structure that can be used include polyether polyols having an oxyethylene structure, such as polyoxyethylene glycol, polyoxyethylene polyoxypropylene glycol, polyoxyethylene polyoxytetramethylene glycol, etc. These compounds may be used alone or in combination of two or more.
[0053] Examples of emulsifiers that can be used when obtaining the aqueous urethane resin that is forcibly dispersed in water include nonionic emulsifiers such as polyoxyethylene nonylphenyl ether, polyoxyethylene lauryl ether, polyoxyethylene styrylphenyl ether, polyoxyethylene sorbitol tetraoleate, and polyoxyethylene-polyoxypropylene copolymers; anionic emulsifiers such as fatty acid salts such as sodium oleate, alkyl sulfate ester salts, alkylbenzene sulfonates, alkyl sulfosuccinates, naphthalene sulfonates, polyoxyethylene alkyl sulfates, sodium alkanesulfonates, and sodium alkyldiphenyl ether sulfonates; and cationic emulsifiers such as alkylamine salts, alkyltrimethylammonium salts, and alkyldimethylbenzylammonium salts. These emulsifiers may be used alone or in combination of two or more.
[0054] Specifically, the urethane resin aqueous dispersion may be one obtained from raw materials used for producing the aqueous urethane resin having a polyisocyanate, a polyol, and the hydrophilic group described above. The reaction may be a known urethane-forming reaction.
[0055] Examples of the polyisocyanate include aromatic polyisocyanates such as phenylene diisocyanate, tolylene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, naphthalene diisocyanate, polymethylene polyphenyl polyisocyanate, and carbodiimidized diphenylmethane polyisocyanate; and aliphatic or alicyclic polyisocyanates such as hexamethylene diisocyanate, lysine diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, dimer acid diisocyanate, and norbornene diisocyanate. These polyisocyanates may be used alone or in combination of two or more.
[0056] Examples of the polyol that can be used include polyether polyol, polyester polyol, polyacrylic polyol, polycarbonate polyol, polybutadiene polyol, etc. These polyols may be used alone or in combination of two or more kinds.
[0057] "Polyester resin" The polyester resin may be a polyester resin obtained by polycondensation reaction of one or more polyols and one or more polycarboxylic acids. The polyols may be ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, pentyl glycol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, poly Examples of the monomer include ethylene glycol, dipropylene glycol, polypropylene glycol, 2-methyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-methyl-1,4-butanediol, 2-ethyl-1,4-butanediol, 2-methyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 3-methyl-1,5-heptanediol, hydrogenated bisphenol A, and an adduct of bisphenol A with propylene oxide or ethylene oxide. Specific examples of polycarboxylic acids include unsaturated dibasic acids and their anhydrides, such as maleic acid, maleic anhydride, fumaric acid, itaconic acid, and citraconic acid; phthalic acid, phthalic anhydride, halogenated phthalic anhydrides, isophthalic acid, terephthalic acid, nitrophthalic acid, tetrahydrophthalic acid, tetrahydrophthalic anhydride, endomethylenetetrahydrophthalic anhydride, halogenated phthalic anhydrides, and esters thereof; hexahydrophthalic acid, hexahydrophthalic anhydride, hexahydroterephthalic acid, hexahydroisophthalic acid, 1,4-cyclohexanedicarboxylic acid, and the like. Examples of the saturated dibasic acids and their anhydrides include carboxylic acid, 1,3-cyclohexanedicarboxylic acid, methylhexahydrophthalic acid, HET acid, 1,1-cyclobutanedicarboxylic acid, oxalic acid, succinic acid, succinic anhydride, malonic acid, glutaric acid, adipic acid, azelaic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,12-dodecanedioic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid anhydride, and 4,4'-biphenyldicarboxylic acid. In order to enhance the affinity for fibers, it is preferable to introduce an ionic group into the polyester resin. Examples of the ionic group include, but are not limited to, a sulfonate group, a carboxylate group, and a phosphate group. As a method for introducing an ionic group into a polyester resin, for example, in the case of carboxylic acid, after polymerizing the polyester resin, one or more of trimellitic anhydride, phthalic anhydride, pyromellitic anhydride, succinic anhydride, maleic anhydride, 1,8-naphthalic anhydride, 1,2-cyclohexanedicarboxylic anhydride, cyclohexane-1,2,3,4-tetracarboxylic acid-3,4-anhydride, ethylene glycol bisanhydrotrimellitate, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, naphthalene-1,8:4,5-tetracarboxylic dianhydride, and the like can be added and reacted under normal pressure and nitrogen atmosphere.
[0058] "Silicone resin" The silicone resin is not particularly limited, but examples thereof include organopolysiloxanes having dimethylsiloxane as a main constituent unit, etc. In order to impart water solubility or water dispersibility to the organopolysiloxane, a hydroxyl group or other functional group may be introduced as necessary.
[0059] "Cationic resin" The cationic resin according to the present embodiment contains a cationic group. Examples of the cationic group include an amino group (e.g., a primary amino group, a secondary amino group, and a tertiary amino group) and a quaternary ammonium group. The tertiary amino group may form an aromatic heterocycle (e.g., a pyridine ring). The secondary amino group may form a heterocyclic amine group (e.g., a piperidine ring and a pyrrolidine ring). The cationic group is preferably an amino group or a quaternary ammonium group, and examples of the cationic group include a trimethylammonium group, a dimethylamino group, a pyridyl group, a group represented by the following chemical formula (A), and -NH2. In the following chemical formula, * indicates a bond. The cationic group may form a salt with an acid (e.g., hydrochloric acid and acetic acid) or a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom).
[0060] [ka]
[0061] Specific examples of the cationic resin include polyalkylene polyamines, polyamide compounds, modified polyamide compounds, polyamidoamine-epihalohydrin or formaldehyde condensation reaction products, polyamine-epihalohydrin or formaldehyde condensation reaction products, polyamide polyurea-epihalohydrin or formaldehyde condensation reaction products, polyamine polyurea-epihalohydrin or formaldehyde condensation reaction products, polyamidoamine polyurea-epihalohydrin or formaldehyde condensation reaction products, polyamide polyurea compounds, polyamine polyurea compounds, Examples of such polyallylamines include polyarylamines such as polyarylamine polyurea compounds, polyarylamine polyurea compounds, polyarylamine compounds, polyethyleneimine, polyvinylpyridine, amino-modified acrylamide compounds, polyvinylamine, polydiallyldimethylammonium chloride; allylamine hydrochloride polymers, allylamine amidosulfate polymers, polyarylamine hydrochloride-diallylamine hydrochloride copolymers consisting of primary and secondary amines, allylamine hydrochloride-dimethylallylamine hydrochloride copolymers consisting of primary and tertiary amines, and allylamine-dimethylallylamine copolymers.
[0062] <<Cationic resin derived from cationic group-containing unsaturated monomer>> The cationic resin preferably contains a specific repeating unit (hereinafter, sometimes referred to as repeating unit (1)) derived from a cationic group-containing unsaturated monomer. The cationic resin may contain only the repeating unit (1) as a repeating unit, but preferably contains the repeating unit (1) and a repeating unit (2) derived from an unsaturated monomer having no cationic group. When the cationic resin contains the repeating unit (2) in this way, the affinity between the solvent of the pretreatment liquid and the cationic resin tends to be appropriately reduced. As a result, the stability of the pretreatment liquid as an emulsion can be improved.
[0063] The cationic group-containing unsaturated monomer has, for example, a cationic group and a polymerizable group (for example, a vinyl group, an allyl group, and a (meth)acryloyl group). The number of cationic groups in the cationic group-containing unsaturated monomer is preferably 1. The number of polymerizable groups in the cationic group-containing unsaturated monomer is preferably 1 or 2. As a specific cationic group-containing unsaturated monomer, dimethylaminopropylacrylamide methyl chloride quaternary salt is preferred.
[0064] The content of the repeating unit (1) in the cationic resin is preferably 10% by mass or more and 60% by mass or less, more preferably 25% by mass or more and 45% by mass or less. By making the content of the repeating unit (1) 10% by mass or more, it is possible to impart sufficient cationicity to the cationic resin. By making the content of the repeating unit (1) 60% by mass or less, the affinity between the solvent of the pretreatment liquid and the cationic resin tends to be appropriately reduced. As a result, it is possible to improve the stability of the pretreatment liquid as an emulsion.
[0065] Examples of the unsaturated monomers without a cationic group include vinyl compounds, (meth)acrylic acid, (meth)acrylic acid alkyl esters, (meth)acrylic acid cycloalkyl esters, and ethylenically unsaturated carboxylic acids. Examples of the vinyl compounds include ethylene, propylene, and styrene. Examples of the (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. Examples of the (meth)acrylic acid cycloalkyl esters include cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, and cyclooctyl (meth)acrylate. Examples of the ethylenically unsaturated carboxylic acids include maleic acid, itaconic acid, citraconic acid, and phthalic acid. The ethylenically unsaturated carboxylic acids may be anhydrides.
[0066] In the cationic resin, the content of the repeating unit (2) is preferably 40% by mass or more and 90% by mass or less, more preferably 55% by mass or more and 75% by mass or less. By setting the content of the repeating unit (2) to 40% by mass or more and 90% by mass or less, the affinity between the solvent of the pretreatment liquid and the cationic resin tends to be appropriately reduced. As a result, the stability of the pretreatment liquid as an emulsion can be improved.
[0067] <<Cationic urethane resin>> The cationic urethane resin according to this embodiment has a cationic group to impart good water dispersion stability in water.
[0068] As the cationic group, for example, a tertiary amino group can be used. The tertiary amino group can be a group in which a part or all of the tertiary amino group is neutralized with acetic acid, propionic acid, or the like, or a group in which a quaternizing agent such as dimethyl sulfate, diethyl sulfate, methyl chloride, or ethyl chloride is used to quaternize the tertiary amino group. The cationic group may be present at the molecular terminal of the urethane resin, in the main chain structure constituting the urethane resin, or in a side chain of the urethane resin as the main chain.
[0069] The cationic groups are preferably present in a range of 10 mmol / kg to 1,000 mmol / kg relative to the entire cationic urethane resin in order to impart good aqueous dispersion stability to the cationic urethane resin in water, and more preferably present in a range of 30 mmol / kg to 700 mmol / kg.
[0070] As the cationic urethane resin, it is preferable to use one having a structure represented by the following general formula [I] containing a cationic group, in order to enhance the function as a binder by strengthening the interaction with the fibers.
[0071] [ka]
[0072] [In the formula, R 1 R represents an alkylene group having an aliphatic or alicyclic structure, a residue of a dihydric phenol, or a polyoxyalkylene group; 2 and R 3 each independently represents an alkyl group having an aliphatic or alicyclic structure, 4 represents a hydrogen atom or a residue of a quaternizing agent introduced by a quaternization reaction, as X - represents an anionic counter ion.
[0073] The cationic urethane resin may have one or more groups selected from the group consisting of a hydrolyzable silyl group and a silanol group.
[0074] [Other additives] The fiber treatment composition according to the present embodiment may further contain other additives. The fiber treatment composition according to the present embodiment may further contain additives such as fillers, preservatives, colorants, defoamers, foaming agents, dispersants, emulsifiers, flow regulators, plasticizers, pH regulators, various oils, thickeners, crosslinking agents, antioxidants, UV absorbers, dispersants, water repellents, and leveling agents, within the scope of not impairing the effects of the present invention. Furthermore, additives such as antibacterial agents, antiviral agents, deodorants, deodorants, softeners, and fragrances may further be contained. These additives may be used alone or in combination of two or more. From the viewpoint of improving the properties of the fiber processed product, the fiber treatment composition according to the present embodiment may contain only a crosslinking agent, if necessary, but it is also possible to improve the fixing property by further containing a binder and a crosslinking agent. Moreover, from the viewpoint of facilitating the treatment in the adhesion step described later, the fiber treatment composition according to the present embodiment may further contain a thickener. The crosslinking agent may be an aqueous crosslinking agent that is expected to crosslink with SACRAN having a carboxyl group. Examples of the aqueous crosslinking agent include EPOCROS WS-500 manufactured by Nippon Shokubai Co., Ltd., PROMINATE XC-830 manufactured by Aica Kogyo Co., Ltd., and Carbodilite V-02-L2 manufactured by Nisshinbo Chemical Co., Ltd. When the crosslinking agent is contained, an example of a binder that may be contained at the same time is DEXCEL HPS PAD 602, an acrylic resin for fiber processing manufactured by DIC Corporation. When the above-mentioned crosslinking agent or binder is contained, an example of a thickener that is simultaneously contained therein is sodium carboxymethylcellulose / CMC Daicel 1350 manufactured by Daicel Miraize Co., Ltd. When the fiber treatment composition is applied by a screen printing method, the viscosity of the composition can be adjusted as desired using a thickener, thereby enabling good application. When the fiber treatment composition according to the present embodiment further contains a binder and a crosslinking agent, the content of the binder in the fiber treatment composition is preferably as described above as "content of the binder in the fiber treatment composition". The content of the crosslinking agent in the fiber treatment composition is preferably 0.05 to 20% by mass, more preferably 0.5 to 10.0% by mass. When a thickener is contained, the content of the thickener in the fiber treatment composition can be arbitrarily adjusted depending on the type and amount of the binder and crosslinking agent to be blended at the same time, but for example, it is preferably 0.1 to 25.0% by mass, more preferably 1 to 10% by mass.
[0075] [water] The water according to the present embodiment may be, for example, ion-exchanged water, RO water, distilled water, or pure water. Industrial water or groundwater may also be used depending on the water quality. In addition, an aqueous solvent that can be mixed with water may also be used within a range that does not impair the performance of the fiber treatment composition according to the present embodiment. Examples of such an aqueous solvent include methanol, ethanol, 2-propanol, and acetone.
[0076] (Textile products) The textile processed product according to the present embodiment includes a textile substrate and a textile treatment agent attached to the textile substrate. The textile treatment agent includes a sulfated polysaccharide. However, the textile substrate does not include rayon. The amount of sulfated polysaccharide attached to various textile substrates depends on the characteristics of the substrate itself, but the amount of sulfated polysaccharide attached after drying is 0.001 to 50.0 parts by mass, 0.002 to 30.0 parts by mass, or 0.003 to 20.0 parts by mass, relative to 100 parts by weight of the textile substrate. The amount is preferably 0.005 to 10.0 parts by mass, more preferably 0.01 to 5.0 parts by mass, even more preferably 0.02 to 3.0 parts by mass, and most preferably 0.03 to 1.0 parts by mass. The amount of the sulfated polysaccharide attached to the fiber substrate is preferably 0.003 parts by mass or more relative to 100 parts by weight of the fiber substrate, since the soil resistance, antistatic properties, water absorption, moisture retention, moisture absorption and moisture release properties of the sulfated polysaccharide can be sufficiently imparted to the fiber substrate, and is preferably 20.0 parts by mass or less, since the performance of the fiber substrate itself is maintained and there is no decrease in the strength and texture of the fiber processed product obtained by using the fiber treatment composition of this embodiment.
[0077] [Fiber base material] The fiber base material according to the present embodiment includes various fibers and blends thereof.
[0078] The fibers are not particularly limited, and include natural fibers and synthetic fibers. The natural fibers are not particularly limited, and include, for example, cotton, silk, hemp, wool, angora and mohair, bamboo fiber, and wool. The synthetic fibers are not particularly limited, and include, for example, polyester fibers, nylon fibers, acrylic fibers, spandex, polyurethane fibers, polyamide fibers (nylon), acetate fibers (diacetate fibers, triacetate fibers, etc.), polylactic acid fibers, aramid fibers, cupra fibers, and regenerated cellulose fibers. From the viewpoint of increasing the adhesion of silicone to the fibers, it is preferable that the fibers contain one or more natural fibers selected from the group consisting of cotton, silk, hemp, wool, angora and mohair, and bamboo fiber. In addition, composite fibers of these fibers can be used.
[0079] The form of the blended fiber product is not particularly limited, and may be, for example, any of staple, filament, tow, yarn, woven fabric, knitted fabric, wadding, nonwoven fabric, paper, and the like.
[0080] Examples of the knitted fabric include flat knitting, rib knitting, and purl knitting, but the fiber base material according to the present embodiment is not limited to these examples. The woven fabric can be produced using the fibers according to this embodiment as the warp threads, the weft threads, or both the warp threads and the weft threads, using a loom or the like. Examples of the weave of the woven fabric include plain weave, twill weave, twill weave, satin weave, and alternating weave, but the fiber base material according to this embodiment is not limited to these examples.
[0081] Specific examples of the fiber substrate according to this embodiment include a blend of cotton and polyester for the base fabric; M2000 manufactured by Shikibo Co., Ltd. and Polyester P-110 (obtained from Shikisen Co., Ltd. as "polyester de chine" fiber for dyeing tests). In addition, the fiber substrate according to this embodiment may be pretreated with a binder to enhance the affinity with the fiber treatment composition of the present invention. In particular, since the sulfated polysaccharide according to this embodiment has an acidic group, a cationic resin is preferred as the pretreatment binder. The preferred aspects of these are the same as those described above in the "cationic resin". The pretreatment method can be carried out according to the "attachment step" and "drying step" described below.
[0082] [Application of textile processed products] The textile product of the present embodiment can be applied to various fields by taking advantage of its excellent water absorption, excellent moisture retention, moisture absorption and release, stain resistance, antistatic properties, and good touch properties. For example, the textile product of the present invention can be suitably used for various applications such as gloves, underwear, socks, shirts, western clothes, sportswear, face masks, surgical masks, materials for paper diapers, cosmetic sheets such as wipe-off lotion sheets, bedding such as hats and inner caps, futon covers, sheets, and pillow covers, curtains, towels and hand towels, cooking aprons and aprons. Furthermore, the textile product of the present invention can be applied to applications requiring antistatic properties such as curtains, suit linings, coats, work clothes (working wear) worn at manufacturing sites, clean room wear, and painting clothes. Furthermore, the textile product of the present invention can be applied to applications requiring comfort such as bandages, elbow and knee joint supports, medical white coats, arm covers, arm slings, leg covers, triangular bandages, medical gauze, and bedding. It can be used for applications requiring comfort and slipperiness, such as stockings, tights, neckties, dresses / drapes, etc. Other applications include rugs / carpets / mats, wall materials, padding, filters, etc.
[0083] (Method of manufacturing textile products) The method for producing a textile product of this embodiment includes treating a textile substrate with the above-described fiber treatment composition of this embodiment to produce a textile product as described below. The method for producing a textile product of this embodiment includes an attachment step of attaching the fiber treatment composition to the textile substrate, and a drying step of removing water from the textile substrate to which the fiber treatment composition has been applied. The method for producing a textile product of this embodiment is characterized by being at least one method selected from the group consisting of the following (I) to (III): (I) before the adhesion step, a step of pretreating a fiber substrate with a fiber pretreatment composition containing a cationic resin to obtain a pretreated fiber substrate, The applying step is a step of applying the fiber treatment composition to the pre-treated fiber substrate. (II) The fiber treatment composition further contains a crosslinking agent, and the drying step includes a heat treatment step at a temperature in the range of 80°C to 260°C. (III) The drying step includes a heat treatment step using high-temperature steam at a temperature range of 120° C. or higher. The fiber base material according to this embodiment is similar to the fiber base material described above, and the preferred aspects are also similar.
[0084] [Attachment process] As the adhesion method in the adhesion step according to this embodiment, various known methods can be adopted without particular limitation, and examples thereof include an application method in which the fiber treatment composition according to this embodiment is applied to a fiber for treatment, and an immersion method in which a fiber is immersed in the fiber treatment composition according to this embodiment for treatment. Examples of the coating method include a direct coating method, a spray coating method, a roll coater method, a slot coater method, a knife coating method, a printing method, a roll transfer method, a screen printing method, etc. Examples of the immersion method include a horizontal roller method, a metering roller method, a screen conveyor method, a foam method, etc. For example, when fibers such as nonwoven fabrics are treated with the fiber treatment agent of the present invention, the processing method may include a spray coating method, a print method, a roll transfer method, a horizontal roller method, a metering roller method, a screen conveyor method, a foam method, a screen printing method, etc. For example, when fibers such as woven fabrics are treated with the fiber treatment agent of the present invention, the processing method may include a direct coating method, a spray coating method, a roll coater method, a slot coater method, a knife coating method, a screen printing method, etc. For example, when fibers are formed into a sheet shape to prepare a web, and the web is further bonded or entangled to form a cloth, the fiber treatment may be performed on the fibers before they are made into a web, or may be performed after the fibers are made into a web by various methods. The fiber web forming method may be any of various known methods without particular limitation, and may include, for example, an air laying method. Furthermore, prior to treatment with the fiber treatment composition of the present invention, the fiber may be pre-treated with a binder or the like in order to enhance the adhesion of the fiber treatment composition of the present invention. Examples of processing methods for pre-treating with a binder or the like include a spray coating method, a printing method, a roll transfer method, a horizontal roller method, a metering roller method, a screen conveyor method, a foam method, a screen printing method, a dipping method, etc. Furthermore, the above processing methods may be repeated multiple times to treat the fiber surface in a layered manner, and then the fiber treatment composition of the present invention may be adhered to the fiber.
[0085] [Preliminary processing process] Furthermore, a pretreatment step of treating with a fiber pretreatment agent may be included prior to treatment with the fiber treatment agent of the present invention in order to enhance the adhesion of the fiber treatment agent of the present invention. The fiber pretreatment agent may contain a cationic resin, or the fiber pretreatment agent may contain a binder. The cationic resin and binder contained in the fiber pretreatment agent have the same meaning as the "cationic resin" and "binder" contained in the fiber treatment agent of the present invention. The cationic resin may be, for example, an amine-based functional cationic polymer. Specific examples of the amine-based functional cationic polymer include, for example, PAA (polyallylamine) PAA-HCL-10L, PAA-D19-HCL, and PAA-15C manufactured by Nittobo Medical Co., Ltd.; PAS (polyamine) PAS-M-1, PAS-J-81, and PAS-H-10L manufactured by Nittobo Medical Co., Ltd.; PRINTRITE DP 316 manufactured by Lubrizol Japan Co., Ltd.; Boncoat SFC-55 manufactured by DIC Corporation; and Boncoat SFC-571 manufactured by DIC Corporation. The binder contained in the fiber pretreatment agent may contain a cationic resin and another binder that is not a cationic resin. Specific examples of other binders include SP-931 manufactured by DIC Corporation. Depending on the cationic resin used, it may be used alone without a binder, or a suitable binder may be blended to make the resin adhere more firmly.
[0086] In the fiber pretreatment agent, the total amount of the cationic resin is preferably 0.1 to 25 mass%, more preferably 0.5 to 20 mass%, and even more preferably 1 to 10 mass%. When the fiber pretreatment agent contains a cationic resin and another binder that is not a cationic resin, the content of the cationic resin is preferably 0.05 to 12.5 mass%, more preferably 0.2 to 10 mass%, and even more preferably 0.5 to 5 mass%.
[0087] [Drying process] The drying method of the drying step according to the present embodiment includes air drying, reduced pressure drying, pressurized drying, heat drying, or any combination thereof. The drying step according to the present embodiment includes a heat treatment step at a temperature range of 70 to 260°C. This temperature range is preferably 80 to 220°C, more preferably 100 to 200°C, and even more preferably 120 to 180°C. If the heating temperature is too low, the drying may take a long time or may be insufficient. In addition, the washing resistance may be deteriorated. If the heating temperature is too high, the fiber treatment agent of the present invention may be deteriorated. A suitable temperature is appropriately set according to the situation. In addition, if the fiber treatment agent is deteriorated by heating, the fiber treatment agent may be heated in a temperature range where the fiber treatment agent is not deteriorated.
[0088] The pretreatment step includes a deposition step and a drying step. In the attachment step of the pretreatment step, various known methods can be used as the attachment method of the cationic resin or the like without any particular limitation. Examples of the adhesion method include a direct coating method, a spray coating method, a roll coater method, a slot coater method, a knife coating method, a printing method, a roll transfer method, a screen printing method, etc. Examples of the immersion method include a horizontal roller method, a metering roller method, a screen conveyor method, a foam method, etc. For example, examples of the processing method when treating fibers such as nonwoven fabrics with the fiber pretreatment agent include spray coating, printing, roll transfer, horizontal roller, metering roller, screen conveyor, foam, and screen printing. For example, examples of the processing method when treating fibers such as woven fabrics with the fiber pretreatment agent include direct coating, spray coating, roll coater, slot coater, knife coating, and screen printing. In addition, when forming fibers into a sheet shape to prepare a web and further bonding or entangling the web to form a cloth, the preliminary fiber treatment may be performed on the fibers before they are made into a web, or may be performed after the fibers are made into a web by various methods. The fiber web method may be any of various known methods without particular limitation, and may be, for example, an air laying method. Furthermore, prior to treatment with the fiber treatment composition of the present invention, the fiber may be pre-treated with a binder or the like in order to enhance the adhesion of the fiber treatment composition of the present invention. Examples of processing methods for pre-treating with a binder or the like include a spray coating method, a printing method, a roll transfer method, a horizontal roller method, a metering roller method, a screen conveyor method, a foam method, a screen printing method, a dipping method, etc. Furthermore, the above processing methods may be repeated multiple times to treat the fiber surface in a layered manner, and then the fiber treatment composition of the present invention may be adhered to the fiber.
[0089] The drying method in the drying step of the preliminary treatment step includes air drying, reduced pressure drying, pressurized drying, heat drying, or any combination thereof. The temperature range when heating during drying is within the range of 80 to 260°C, preferably 80 to 200°C, and more preferably 100 to 180°C. If the heating temperature is too low, drying may take a long time or may be insufficient. If the preliminary treatment with the cationic resin is insufficient, the fiber treatment agent may not be fixed sufficiently, resulting in poor washability. If the heating temperature is too high, the resin used may be altered. Appropriate temperature conditions are set according to the situation. If the resin is altered by heating, it may be heated in multiple steps within a temperature range where the resin is not altered.
[0090] Furthermore, the above pretreatment step may be repeated several times to treat the fiber surface in a layered manner, and then the fiber treatment agent of the present invention may be applied thereto.
[0091] In order to promote adhesion of the fiber treatment agent of the present invention, the heat treatment step of the drying step according to this embodiment may be a heat treatment using high-temperature steam. The base fabric to which the fiber treatment agent is adhered may also be exposed to high-temperature steam such as steam. The exposure to high-temperature steam may be performed after the adhesion step of the fiber treatment agent or after the above-mentioned drying step. The fiber treatment agent of the present invention diffuses and adheres to the inside of the fiber by the water vapor, and further functional improvement can be expected. For example, steam or superheated water vapor can be used as the water vapor. The temperature of the water vapor is within the range of 100 to 260°C, preferably 100 to 200°C, and more preferably 120 to 180°C. If the temperature of the water vapor is too low, the heat treatment may take a long time and may be insufficient. If the temperature of the water vapor is too high, the fiber treatment agent or the base fabric may be deteriorated. A suitable temperature is appropriately set according to the situation. If the material is deteriorated by the heat treatment, the material may be treated in multiple steps within a temperature range where the material is not deteriorated. Any type of generator can be used as long as it can generate high-temperature steam. In addition to pressure cookers and autoclaves, superheated steam generators, superheated steam batch furnaces, nozzle-type steam sprayers, and the like can be used in this heat treatment process. In such cases, the base fabric may be treated by exposing it to high-temperature steam, or the surface of the base fabric may be treated in a pinpoint manner. The drying step according to the present embodiment may include a normal heat treatment step and the heat treatment with high-temperature steam. The temperature range of the normal heat treatment step may be 70 to 260°C, preferably 80 to 220°C, and more preferably 100 to 200°C.
[0092] In addition, in order to promote adhesion of the fiber treatment agent of the present invention after the drying step and improve washing resistance, the fiber may be heated in a temperature range in multiple steps. For example, the fiber may be treated twice at the same temperature within the above temperature range. An example of the method is, for example, a method of treating the fiber at 120°C for 1 minute, followed by additional treatment at 150°C for 1 minute 30 seconds. The first treatment temperature may be outside the above range, and the second and subsequent treatments may be performed at temperatures within the above range. An example of the method is, for example, a method of treating the fiber at 70°C, followed by treatment with high-temperature steam such as steam at 160 to 180°C. The drying step in the present invention has the purpose of removing excess moisture and solvent, as well as the effect of promoting adhesion of sulfated polysaccharide to fibers and promoting film formation of sulfated polysaccharide, so it is desirable to select an optimal drying step depending on the type of sulfated polysaccharide and the type of fiber substrate.
[0093] [Specific examples of manufacturing methods for textile processed products] The manufacturing method of this embodiment will be further described below using a first embodiment, a second embodiment, and a third embodiment.
[0094] [First embodiment] In the manufacturing method of the first embodiment, before treating the fiber substrate with the fiber treatment composition of the present embodiment described above, the method further includes a step of pretreating the fiber substrate with a fiber pretreatment composition containing a cationic resin to obtain a pretreated fiber substrate. That is, the manufacturing method of the first embodiment includes a step of obtaining a pre-treated fiber substrate by treating a fiber substrate with a fiber pre-treatment composition containing a cationic resin, a step of adhering the fiber treatment composition of this embodiment to the pre-treated fiber substrate, and a drying step of removing water from the fiber substrate to which the fiber treatment composition of this embodiment has been applied. The meanings and preferred forms of the fiber substrate, the fiber treatment composition of the present embodiment, the application step, and the drying step are the same as those described above. The fiber pretreatment composition containing the cationic resin may have the same composition as the fiber treatment composition of this embodiment, except that it contains a cationic resin and does not contain a sulfated polysaccharide such as sacran. The method for obtaining a pretreated fiber substrate using the fiber pretreatment composition may be the same as the method for obtaining a fiber processed product of this embodiment, except that the fiber pretreatment composition is used. The method for obtaining a pre-treated fiber substrate may include, for example, a pre-treatment application step of applying the fiber pre-treatment composition to the fiber substrate, and a pre-treatment drying step of removing water from the fiber substrate to which the fiber pre-treatment composition has been applied. The pre-treatment application step and the pre-treatment drying step may be the same as the application step and the drying step described in the method for producing a fiber processed product of this embodiment.
[0095] [Second embodiment] In the manufacturing method of the second embodiment, the fiber treatment composition of the present embodiment further contains a binder or a crosslinking agent, or both, to promote adhesion to the fiber. In the drying step, the heating temperature range is 80°C to 260°C. The content of the sulfated polysaccharide in the fiber treatment composition of the second embodiment is preferably the same as the above-mentioned "content of the sulfated polysaccharide in the fiber treatment composition." The content of the crosslinking agent in the fiber treatment composition of the second embodiment is preferably the same as the above-mentioned "content of the crosslinking agent in the fiber treatment composition." Furthermore, when a binder is contained, the content of the binder in the fiber treatment composition of the second embodiment is preferably the same as the above-mentioned "content of binder in the fiber treatment composition". The manufacturing method of the second embodiment includes an application step of applying the fiber treatment composition of the second embodiment to the fiber substrate, and a drying step of removing water from the fiber substrate to which the fiber treatment composition of the second embodiment has been applied. In the drying step, the heating temperature ranges from 80°C to 260°C, preferably from 80°C to 200°C, and more preferably from 100°C to 180°C.
[0096] [Third embodiment] In the manufacturing method according to the third embodiment, the drying step includes a heat treatment step using high-temperature steam in the temperature range of 120° C. or higher. The heat treatment step using high-temperature steam here has the same meaning as the heat treatment step using high-temperature steam described above. That is, the manufacturing method of the third embodiment includes an application step of applying the fiber treatment composition to the fiber substrate, and a drying step of removing water from the fiber substrate to which the fiber treatment composition has been applied. The drying step of the third embodiment includes a heat treatment step using high-temperature steam in the temperature range of 100° C. or higher. The temperature range is preferably 100 to 200° C., and more preferably 120 to 180° C. The drying step of the third embodiment may or may not include a heat treatment step at 70° C. or higher before the heat treatment step with high-temperature steam.
[0097] [Dispersible fiber treatment agent] The dispersible fiber treatment agent according to the present embodiment is obtained by a dispersion treatment, The dispersible fiber treating agent according to this embodiment has a rate of change (%) in viscosity of the fiber treating agent before and after dispersion treatment, represented by the following formula (1), of 20% or more.
[0098] [(AB) / A]×100……(1) (In formula (1), A is the viscosity (milliPascal seconds (mPa s)) of the fiber treatment agent before dispersion treatment, and B is the viscosity (milliPascal seconds (mPa s)) of the dispersible fiber treatment agent after dispersion treatment.) The dispersible fiber treatment agent of the present embodiment may further contain other ingredients such as a moisturizer and a preservative, in addition to the sulfated polysaccharide and water.
[0099] The content of the sulfated polysaccharide is 5.0% or less, and preferably 3.0% or less, based on the total mass of the dispersible fiber treatment agent.
[0100] <Viscosity of dispersible fiber treatment agents> The change rate (%) of viscosity of the dispersible fiber treatment agent before and after the dispersion treatment according to this embodiment is 20% or more. If the change rate of viscosity is 20% or more, the inconvenience in handling during blending work during production and the like and the adverse effects due to insufficient penetration can be sufficiently suppressed. On the other hand, in order to maintain the effect of containing sulfated polysaccharides, it is preferable that the dispersible fiber treatment agent according to this embodiment after dispersion treatment has a certain degree of viscosity, and therefore the rate of change in viscosity is preferably 85% or less. The rate of change (%) of viscosity is expressed by the following formula (1).
[0101] [(AB) / A]×100……(1)
[0102] In formula (1), A is the viscosity (milliPascal seconds (mPa s)) of the fiber treatment agent before dispersion treatment, B is the viscosity (milliPascal seconds (mPa·s)) of the dispersible fiber treatment agent after dispersion treatment.
[0103] The rate of change (%) in viscosity before and after the dispersion treatment of the dispersible fiber treatment agent according to this embodiment is more preferably 30% or more, and more preferably 75% or less.
[0104] [Viscosity measurement] For example, the viscosity of the solution can be measured at a temperature of 20°C to 25°C using a B-type viscometer (DV2T manufactured by Eiko Seiki Co., Ltd.) or an E-type viscometer (VISCOMETER TV-25 TYPE L, VISCOMETER TVE-22LT, etc. manufactured by Toki Sangyo Co., Ltd.).
[0105] (Method of producing fiber treatment composition) The method for producing the fiber treatment composition of this embodiment is a method for producing a fiber treatment composition by preparing a dispersible fiber treatment agent using the "method for producing a dispersible fiber treatment agent" according to this embodiment described below, and then mixing water and other additives with the obtained dispersible fiber treatment agent as necessary.
[0106] [Method of producing dispersible fiber treatment agent] The method for producing a dispersible fiber treatment agent according to the present embodiment includes the steps of: mixing the sulfated polysaccharide with water and stirring the resulting mixture with a stirrer; and Dispersing the stirred mixed composition using a disperser. In addition, in this embodiment, it is preferable that the dispersible fiber treatment agent in the manufacturing method of a dispersible fiber treatment agent of this embodiment is a dispersible fiber treatment agent that exhibits a rate of change in viscosity (%) of 20% or more before and after dispersion treatment, as represented by the above formula (1), particularly as described in the above section [Dispersible fiber treatment agent].
[0107] <Step of stirring with a stirrer> Mixing refers to stirring substances and mixing multiple types of substances together. In this embodiment, the stirring step refers to a step of mixing the sulfated polysaccharide and water by stirring a mixed composition containing the sulfated polysaccharide and water in a stirrer. The stirrer is not particularly limited as long as it can produce the effects of this embodiment and can be appropriately selected depending on the purpose. Examples of the stirrer include a homodisper, an emulsifier, a line mixer, a three-one motor, and a magnetic stirrer.
[0108] The conditions for the stirring step are not particularly limited and can be appropriately selected depending on the purpose as long as the effects of the present embodiment are achieved, but for example, the stirring time is preferably 1 to 48 hours, and the temperature during stirring is preferably 20 to 80°C.
[0109] <Dispersion process using a dispersing machine> Dispersion refers to the process of reducing the particle size of a substance by applying impact or shear forces to the substance, and dispersing the smaller particles of a substance within one phase of another substance. In this embodiment, the dispersing step refers to a step of stirring the mixed composition after stirring in a disperser while applying impact force or shear force, thereby reducing the particle size of the sulfated polysaccharide and dispersing the smaller particles of the sulfated polysaccharide in water. When the mixed composition is mixed using only the above-mentioned stirrer, the sulfated polysaccharides are present in the water as large particle sizes and in a fibrous entangled state. However, by using a disperser, the sulfated polysaccharides can be dispersed in the water as smaller particles. The disperser is not particularly limited as long as it can achieve the effects of this embodiment, and can be appropriately selected depending on the purpose. Examples of the disperser include a type that utilizes the kinetic energy of spherical dispersion media with a diameter of about 0.1 to 10 mm made of steel, stainless steel, zirconia, alumina, silicon nitride, glass, etc., a type that utilizes shear force due to mechanical stirring, a type that utilizes the force generated by pressure changes, flow path changes, or collisions of the flux of the liquid to be treated supplied at high speed, and a dispersion type disperser such as an ultrasonic disperser. More specifically, examples of the media dispersing machine include a sand mill, a bead mill, a pebble mill, a ball mill, a pearl mill, a basket mill, an attritor, a dyno mill, a bore mill, a visco mill, a motor mill, an SC mill, a dry mill, and a paint conditioner. Other examples include a media-less dispersing machine that does not use media, such as an ultrasonic dispersing machine (ultrasonic homogenizer), a high-pressure homogenizer, a nanomizer, and an ultimizer. Other examples include a kneading dispersing machine that applies a strong shear force to disperse the material using a kneading machine such as a roll mill such as a three-roll mill, a Henschel mixer, a pressure kneader, an intensive mixer, a Banbury mixer, or a planetary mixer.
[0110] The conditions in the dispersion step are not particularly limited and can be appropriately selected depending on the purpose as long as the effects of this embodiment are achieved. For example, the dispersion time is preferably 1 to 24 hours. The temperature during dispersion is preferably 1 to 80°C. In the case of dispersion using a disperser that uses spherical dispersion media, for example, the filling rate of the spherical dispersion media in the dispersion chamber is preferably 20 to 90%, and the peripheral speed of the rotor that imparts kinetic energy to the spherical dispersion media is preferably 5 to 20 m / sec.
[0111] A specific embodiment of the dispersion method is, for example, a dispersion method using a wet bead mill operated at a predetermined peripheral speed of the disperser at a predetermined power density, since this method has high dispersion ability and dispersion efficiency. Various conditions such as the type and size (volume) of the apparatus, the type and amount of the dispersed sample (a mixture of sulfated polysaccharide and water), the peripheral speed of the disperser, and the flow rate of the dispersed sample are appropriately set.
[0112] [Textile treatment agent] The fiber treatment agent of this embodiment is formed by adhering the fiber treatment composition of this embodiment to the fiber substrate using the processing method for fiber processed products described below, followed by a drying process to remove water from the adhered fiber treatment composition, and then adhering it to the surface of the fiber substrate. The fiber treatment agent according to this embodiment contains the sulfated polysaccharide contained in the dispersible fiber treatment agent according to this embodiment, and any other additive components contained in the dispersible fiber treatment agent or any other additive components added to the dispersible fiber treatment agent when producing the fiber treatment agent composition of this embodiment. The fiber treatment agent according to this embodiment may or may not contain water. Furthermore, the fiber treatment agent according to this embodiment may contain only the components contained in the dispersible fiber treatment agent. EXAMPLES
[0113] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto.
[0114] "Preparation of fiber treatment composition A-1" (Preparation example A1) 995 parts by mass of ion-exchanged water was added to 5.0 parts by mass of SACRAN (registered trademark) (manufactured by Green Science Materials Co., Ltd., sulfated polysaccharide derived from Aphanothece sacrum, molecular weight: about 2 million to about 20 million) as sulfated polysaccharide, and a 0.5% by mass SACRAN aqueous solution was prepared by stirring at 75 ° C for 8 hours using a three-one motor (FBL600 manufactured by HEIDON) equipped with a propeller shaft. Next, 400 parts by mass of 0.5% by mass SACRAN aqueous solution and 600 parts by mass of ion-exchanged water were stirred at room temperature for 30 minutes using a three-one motor to obtain a 0.2% by mass SACRAN aqueous solution. Next, 250 parts by mass of 0.2% by mass SACRAN aqueous solution and 750 parts by mass of ion-exchanged water were stirred at room temperature for 30 minutes using a three-one motor to obtain a fiber treatment composition A of this preparation example. The content of SACRAN in the fiber treatment composition A, calculated from the blending amounts, was 0.05% by mass. The results are shown in Table 1.
[0115] (Preparation example A2) 250 parts by weight of the 0.2% SACRAN (registered trademark) aqueous solution obtained in Preparation Example A1, 2.5 parts by weight of an aqueous urethane resin dispersion as a binder (DEXCEL HPS PAD708U manufactured by DIC Corporation; non-volatile content 40%), and 747.5 parts by weight of ion-exchanged water were stirred with a three-one motor at room temperature for 30 minutes to obtain Fiber Treatment Agent Composition B of this Preparation Example. The content of SACRAN in the fiber treatment composition A, which was determined from the blending amount, was 0.05% by mass. The content of the binder in the fiber treatment composition A was 0.1% by mass. The content of the binder was 200 parts by mass per 100 parts by mass of SACRAN. The results are shown in Table 1.
[0116] [Table 1]
[0117] "Preparation of textile products for evaluation A-1" (Example A1) <Attachment process> The fiber treatment composition A obtained in Preparation Example A1 was applied to a base fabric (cotton and polyester blend; M2000 manufactured by Shikibo Co., Ltd.) as a fiber substrate at a rate of 80 to 90 g / m using a mangle coater (manufactured by Tsujii Senki Kogyo Co., Ltd.). 2 The coating weight (amount of fiber treatment composition A applied per unit area of base fabric) is 0.04 to 0.05 g / m in terms of SACRAN (registered trademark) weight. 2 A base fabric having fiber treatment composition A adhered thereto was obtained.
[0118] <Drying process> The base fabric having the fiber treatment composition A applied thereto, obtained in the above application step, was subjected to a heat drying treatment at 70° C. for 1 minute to obtain a SAKRAN fiber processed product A as a processed fiber product.
[0119] (Evaluation of textile products) (1)Tactile sensation The texture of the SAKRAN fiber processed products was evaluated by lightly pressing them with the fingers on the following three-level scale (ABC rank), and the results are shown in Table 1.
[0120] A: It is soft and has a moist feel. B: Soft or moist feel. C: No softness or moist feeling.
[0121] (2) Water absorption According to JIS L-1907 Water Absorption Test Method for Textile Products (Dropping Method), a drop of water was dropped from a burette onto the textile product, and the time from when the drop reached the surface of the fiber until the drop was absorbed was measured. The average value of five textile products was rounded off to the nearest integer and rated on the following three levels (ABC rank), and the results are shown in Table 2.
[0122] A: Water absorption time is 5 seconds or less B: Water absorption time is 6 to 8 seconds C: Water absorption time is 9 seconds or more
[0123] (3) Moisture absorption and release According to JIS L-1954:2022, a method for testing the moisture absorption and release properties of fabrics over time, the mass change of the textile processed product was measured over time during the moisture absorption process in which the textile processed product was moved from the low humidity side to the high humidity side, and during the moisture release process in which the textile processed product was moved from the high humidity side to the low humidity side, and the moisture absorption rate and moisture release rate were calculated. The moisture absorption and release properties were each evaluated using the following three levels (ABC rank), and the results are shown in Table 2.
[0124] Hygroscopic A: Moisture absorption rate is 0.45% / min or more B: Moisture absorption rate is 0.40-0.44% / min. C: Moisture absorption rate is 0.39% / min or less
[0125] Moisture release A: Moisture release rate is 0.40% / min or more B: Moisture release rate is 0.35-0.39% / min. C: Moisture release rate is 0.34% / min or less
[0126] (Example A2) <Attachment process> A base fabric having fiber treatment composition B adhered thereto was obtained in the same manner as in Example A1, except that fiber treatment composition B obtained in Preparation Example A2 was used instead of fiber treatment composition A obtained in Preparation Example A1.
[0127] <Drying process> A textile product B was produced in the same manner as in Example A1, except that heat drying was performed at 70° C. for 1 minute, and then heat drying was performed at 130° C. for 1 minute. Evaluations were performed in the same manner as in Example A1, and the results are shown in Table 2.
[0128] (Comparative Example A1) Instead of the textile product A, a base fabric (a blend of cotton and polyester; M2000 manufactured by Shikibo Co., Ltd.) was used as it was, and evaluation was carried out in the same manner as in Example A1. The results are shown in Table 2.
[0129] [Table 2]
[0130] (Consideration) As shown in Table 2, the textile products of Examples A1 and A2 obtained from the textile treatment composition of the present invention were superior in terms of touch, water absorption, moisture absorption and moisture release properties compared to the untreated textile of Comparative Example A1. It is believed that when the textile product of the present invention is used for clothing, for example, it feels good against the skin and reduces stuffiness inside the clothing.
[0131] "Preparation of fiber treatment composition A-2" (Preparation example A3) 995 parts by mass of ion-exchanged water was added to 5.0 parts by mass of SACRAN (registered trademark) (manufactured by Green Science Materials Co., Ltd., sulfated polysaccharide derived from Aphanothece sacrum, molecular weight: approximately 2 million to approximately 20 million) as a sulfated polysaccharide, and the mixture was stirred at 75°C for 8 hours using a three-one motor equipped with a propeller shaft (FBL600 manufactured by HEIDON Co., Ltd.) to obtain a fiber treatment composition C of this preparation example consisting of a 0.5% by mass SACRAN aqueous solution.
[0132] (Preparation example A4) 400 parts by mass of the 0.5% by mass SACRAN (registered trademark) aqueous solution obtained in Preparation Example A3 and 600 parts by mass of ion-exchanged water were stirred with a three-one motor at room temperature for 30 minutes to obtain a 0.2% by mass SACRAN aqueous solution. Next, 100 parts by mass of the obtained 0.2% by mass SACRAN aqueous solution was stirred at room temperature with a homomixer at 3000 rpm, while 0.81 parts by mass SACRAN (manufactured by Green Science Materials Co., Ltd., sulfated polysaccharide derived from Aphanothece sacrum, molecular weight: about 2 million to about 20 million) was gradually added to the SACRAN aqueous solution in small amounts. After all SACRAN was added, the rotation speed was changed to 5000 rpm and stirring was continued for another 30 minutes to obtain a fiber treatment composition D of this preparation example consisting of a 1.0% by mass SACRAN aqueous solution.
[0133] (Preparation example A5) While stirring 100 parts by mass of the 0.2% by mass SACRAN (registered trademark) aqueous solution obtained in Preparation Example A4 at room temperature with a homomixer at 3000 rpm, 1.32 parts by mass of SACRAN (manufactured by Green Science Materials Co., Ltd., sulfated polysaccharide derived from Aphanothece sacrum, molecular weight: about 2 million to about 20 million) was gradually added to the SACRAN aqueous solution in small amounts. After all SACRAN was added, the rotation speed was changed to 5000 rpm and stirring was continued for another 30 minutes to obtain a fiber treatment composition E of this Preparation Example consisting of a 1.5% by mass SACRAN aqueous solution.
[0134] The contents of SACRAN in the fiber treatment compositions C, D, and E obtained in the above Preparation Examples A3, 4, and 5 were 0.5 mass%, 1.0 mass%, and 1.5 mass%, respectively, and each fiber treatment composition did not contain a binder. The results are shown in Table 3.
[0135] (Preparation example A6) 995 parts by mass of ion-exchanged water was added to 5.0 parts by mass of urea, and the solution was stirred until the urea crystals were completely dissolved to prepare a 0.5% by mass urea aqueous solution. Fiber treatment composition F of this preparation example was obtained. The results are shown in Table 3.
[0136] [Table 3]
[0137] "Preparation of textile products for evaluation A-2" (Example A3) <Attachment process> The fiber treatment composition C obtained in Preparation Example A3 above was applied to a polyester P-110 base fabric (obtained from Shikisensha Co., Ltd. as "polyester de chine", a fiber for dyeing tests) at a rate of 70 to 80 g / m using a mangle coater (manufactured by Tsujii Senki Kogyo Co., Ltd.). 2 The coating weight (amount of fiber treatment composition C applied per unit area of base fabric) is 0.3 to 0.4 g / m2 in terms of SACRAN weight. 2 A base fabric having fiber treatment composition C adhered thereto was obtained.
[0138] <Drying process> The base fabric having the fiber treatment composition C applied thereto, obtained in the above application step, was subjected to a heat drying treatment at 70° C. for 1 minute to obtain a SAKRAN fiber processed product C as a processed fiber product.
[0139] (Example A4) <Attachment process> The fiber treatment composition D obtained in Preparation Example A4 above was placed on a screen mesh stencil and applied at 70 to 80 g / m to a polyester P-110 base fabric (obtained from Shikisensha Co., Ltd. as "polyester de chine", a fiber for dyeing tests). 2 The coating weight (amount of fiber treatment composition D applied per unit area of base fabric) is 0.7 to 0.8 g / m in terms of SACRAN weight. 2 A base fabric having fiber treatment composition D adhered thereto was obtained.
[0140] <Drying process> The base fabric having the fiber treatment composition D applied thereto, obtained in the above application step, was subjected to a heat drying treatment at 100° C. for 2 minutes to obtain a SAKRAN fiber processed product D as a processed fiber product.
[0141] (Example A5) <Attachment process> The fiber treatment composition E obtained in Preparation Example A5 above was placed on a screen mesh stencil and applied at 60 to 70 g / m to a polyester P-110 base fabric (obtained from Shikisensha Co., Ltd. as "polyester de chine", a fiber for dyeing tests). 2 The fiber treatment composition E was applied at a basis weight (amount of fiber treatment composition E applied per unit area of base fabric), equivalent to a basis weight of 0.9 to 1.1 g / m2 in terms of SACRAN. A base fabric having fiber treatment composition E attached thereto was obtained.
[0142] <Drying process> The base fabric having the fiber treatment composition E applied thereto, obtained in the above application step, was subjected to a heat drying treatment at 100° C. for 2 minutes to obtain a SACRAN fiber processed product E as a processed fiber product.
[0143] (Example A6) <Attachment process> The fiber treatment composition D obtained in Preparation Example A4 above was placed on a screen mesh stencil and applied at 70 to 80 g / m to a polyester P-110 base fabric (obtained from Shikisensha Co., Ltd. as "polyester de chine", a fiber for dyeing tests). 2 The coating weight (amount of fiber treatment composition D applied per unit area of base fabric) is 0.7 to 0.8 g / m in terms of SACRAN weight. 2 A base fabric having fiber treatment composition D adhered thereto was obtained.
[0144] <Heat treatment process> The base fabric having the fiber treatment composition D applied thereto, obtained in the above application step, was subjected to a heat treatment with high-temperature steam at 160° C. As a fiber processed product, a SACRAN fiber processed product F was obtained.
[0145] (Example A7) <Attachment process> The fiber treatment composition E obtained in Preparation Example A5 above was placed on a screen mesh stencil and applied at 60 to 70 g / m to a polyester P-110 base fabric (obtained from Shikisensha Co., Ltd. as "polyester de chine", a fiber for dyeing tests). 2 The coating weight (amount of fiber treatment composition E applied per unit area of base fabric) is 0.9 to 1.1 g / m2 in terms of SACRAN weight. 2 A base fabric having fiber treatment composition E adhered thereto was obtained.
[0146] <Heat treatment process> The base fabric having the fiber treatment composition E applied thereto obtained in the above-mentioned application process was heat-treated with high-temperature steam at 160°C, and then dried at 70°C for 3 minutes to obtain a Sakuran fiber processed product G as a fiber processed product.
[0147] (Comparative example A2) <Attachment process> The fiber treatment composition F obtained in Preparation Example A6 was applied to a polyester P-110 base fabric (obtained from Shikisensha Co., Ltd. as "polyester de chine", a fiber for dyeing tests) at a rate of 70 to 80 g / m using a mangle coater (manufactured by Tsujii Senki Kogyo Co., Ltd.).2 The coating weight (amount of fiber treatment composition F applied per unit area of base fabric) is 0.3 to 0.4 g / m2 in terms of urea weight. 2 A base fabric having fiber treatment composition F adhered thereto was obtained.
[0148] <Drying process> The base fabric having the fiber treatment composition F applied thereto, obtained in the above application step, was subjected to a heat drying treatment at 70° C. for 1 minute to obtain a urea fiber product H as a fiber product.
[0149] (Comparative example A3) Using only water that did not contain the above-mentioned sulfated polysaccharides or binders, the adhesion process and drying process were carried out in the same manner as in Example A3 on a polyester P-110 base fabric (obtained from Shikisen Co., Ltd. as "polyester de chine", a fiber for dyeing tests), to obtain a polyester base fabric (without Sakuran) that was only water-treated and had no Sakuran attached.
[0150] (Evaluation of textile products) The moisture absorption, moisture release and stain resistance of the SACRAN (registered trademark) fiber processed product C of Example A3 were evaluated by the following methods, and the results are shown in Table 5. Furthermore, Examples A4 to A7 and Comparative Examples A2 to A3 were evaluated by the same methods as those of Example A3, and the results are shown in Table 5. The SACRAN fiber processed product C of Example A3 was evaluated for electrostatic property (antistatic property) by the following method, and the results are shown in Table 6. The comparative example A3 was also evaluated by the same method as Example A3, and the results are shown in Table 6.
[0151] (1) Moisture absorption and release According to JIS L-1954:2022, a method for testing moisture absorption and release over time for fabrics, the mass change of the fabric was measured over time during the moisture absorption process in which the fabric was moved from a low humidity side to a high humidity side, and during the moisture release process in which the fabric was moved from a high humidity side to a low humidity side, and the moisture absorption rate, moisture release rate, and moisture absorption speed and moisture release speed of the test fabric were calculated. Moisture absorption and release were evaluated in the following three stages (ABC rank).
[0152] Hygroscopic A: Moisture absorption rate is 0.60% or more or moisture absorption rate is 0.10% / min or more B: Moisture absorption rate is 0.36-0.59% or moisture absorption rate is 0.06-0.09% / min C: Moisture absorption rate is 0.35% or less or moisture absorption rate is 0.05% / min or less
[0153] Moisture release A: Moisture release rate is 0.60% or more or moisture release rate is 0.10% / min or more B: Moisture release rate is 0.36-0.59% or moisture release rate is 0.06-0.09% / min C: Moisture release rate is 0.35% or less or moisture release rate is 0.05% / min or less
[0154] (2) Antifouling Using JIS L-1919:2012, A-2 method for testing the stain resistance of textile products as a reference, a powdered contaminant was prepared and a simple evaluation test was conducted for stains caused by fine powders such as dust and dirt. A test piece of fabric sample of each textile product and the contaminant were placed in a polyethylene bag, and the inflated bag was rotated to determine the "resistance to staining" of the fabric, and the sample was then washed to determine the "ease of removing stains."
[0155] <Powder-like contaminants> [Table 4]
[0156] <Resistance to dirt> 0.25g of the powdered contaminant was placed in a polyethylene bag with a zipper (Unipack F-8, manufactured by Nippon Seisakusho Co., Ltd.), one test piece was then placed inside, and air was sealed into the bag using an air pump until the bag was completely inflated. The pillow-shaped bag was then fixed to a rotating machine and rotated at a speed of 60±2 revolutions per minute for 60 minutes. Next, while changing the four corners of the test piece, the center of the back surface of the test piece was flicked five times with a finger to remove excess powder stain, and the degree of staining of the test cloth was judged. When flicking with a finger, two fingers were used, and the test piece was rotated 90 degrees after each flick, for a total of five flicks.
[0157] <Easy to remove dirt> The washing procedure was carried out with reference to the method specified in JIS L-0217, Appendix 1 [Test methods by symbol - Washing method (water washing)], No. 103 method. The detergent used in the washing procedure was JAFET standard blend detergent available from the Japan Textile Evaluation Technology Council. After washing, rinsing, and spin-drying, the test pieces were hung to dry at room temperature. After drying, the degree of contamination of the test pieces was evaluated.
[0158] <Assessment of stain resistance> The color difference visible between the test pieces before exposure to the contaminant and after contamination, washing and drying was judged using the staining gray scale specified in JIS L-0805. When the staining density was not uniform, the judgment was usually made on the average of the entire test piece. When the test piece was curled up and the staining density varied greatly depending on the part, the darker part was judged. When the staining density was darker in the wrinkled part of the test piece, that part was excluded from the judgment. Based on the grade values obtained from the staining gray scale, the stain resistance in terms of how easily stains are removed and how easily stains are removed was evaluated into the following three levels (ABC rank).
[0159] Stain resistance / resistance to dirt A (Good): Grayscale value of grade 4 or higher B (fairly good); grayscale value grade 3~3-4 C (poor): Grayscale value of 2-3 or lower
[0160] Stain resistance / ease of removing stains A (Good): Grayscale value of grade 4 or higher B (fairly good); grayscale value grade 3~3-4 C (poor): Grayscale value of 2-3 or lower
[0161] (3) Electrostatic properties (antistatic properties) In accordance with JIS L-1094; Test method for electrostatic properties of woven and knitted fabrics, the textile products were subjected to the following methods A and B in an environment of 20°C ± 2°C temperature and (40±2)% relative humidity.
[0162] Method A: Half-life measurement method; Evaluation of the ease of dissipating static electricity Using a half-life measuring device, a test piece of cloth (45 mm x 45 mm) was charged with an applied voltage of 10 KV, and the time (S) until the charged voltage decayed to half was measured as the half-life.
[0163] Method B: Friction-charged potential measurement method; Evaluation of resistance to static electricity accumulation Using a friction charging voltage measuring device, a test cloth piece (50 mm x 80 mm) was attached to a rotating drum and rubbed with a friction cloth (wool or cotton), and the charging voltage (V) / friction charging voltage was measured one minute after the start of friction.
[0164] Based on the measurements obtained using Methods A and B, the electrostatic properties of the fibers were evaluated based on the criteria of half-life: 10 seconds or less and frictional charging voltage: 2000 V or less, and textile products that met both numerical criteria were deemed to have "good" antistatic properties (antistatic effect).
[0165] [Table 5]
[0166] [Table 6]
[0167] (Consideration) As shown in Tables 5 and 6, the SACRAN (registered trademark) fiber processed products of Examples A3 to A7 obtained from the fiber processing composition containing the sulfated polysaccharide of the present invention were superior in moisture absorption and moisture release properties as well as in soil resistance and antistatic properties compared to the fiber processing composition H containing urea of Comparative Example A2 and the polyester base fabric only not containing the fiber processing agent of Comparative Example A3. In addition to the coating method of immersing the fiber processing composition in a solution state using a mangle coater, high functionality can also be imparted by a screen printing method using a stencil. When the fiber processed products of the present invention are used for, for example, clothing, it is thought that the amount of water vapor in the clothing is controlled to reduce stuffiness, and the surface of the clothing is also less likely to be soiled. Furthermore, it is possible to provide a fiber treatment agent containing a polysaccharide as an ingredient, which has higher biodegradability and safety than synthetic polymer-based functional fiber treatment agents. The sulfated polysaccharide used in the present invention not only has excellent functionality, but also has low bioirritation and is therefore safe, so that the fiber treatment agent of the present invention can be suitably used in fields where safety is important, such as clothing.
[0168] "Preparation of fiber treatment composition B-1" (Preparation example B1) 5.0 parts by mass of SACRAN (registered trademark, manufactured by Green Science Materials Co., Ltd., sulfated polysaccharide derived from Aphanothece sacrum, molecular weight: about 2 million to about 20 million) as sulfated polysaccharide was added to 995 parts by mass of ion-exchanged water, and stirred at 75 ° C for 8 hours using a three-one motor (FBL600 manufactured by HEIDON) equipped with a propeller shaft to prepare a 0.5% by mass SACRAN aqueous solution. Next, 400 parts by mass of the 0.5% by mass SACRAN aqueous solution and 600 parts by mass of ion-exchanged water were stirred at room temperature for 30 minutes using a three-one motor to obtain a 0.2% by mass SACRAN aqueous solution. Next, 250 parts by mass of the 0.2% by mass SACRAN aqueous solution and 750 parts by mass of ion-exchanged water were stirred at room temperature for 30 minutes using a three-one motor to obtain a fiber treatment composition A of this preparation example B. The content of SACRAN in the fiber treatment composition A, calculated from the blending amounts, was 0.05% by mass. The results are shown in Table 7.
[0169] (Preparation example B2) 250 parts by weight of the 0.2% SACRAN aqueous solution obtained in Preparation Example B1, 2.5 parts by weight of an aqueous urethane resin dispersion as a binder (DEXCEL HPS PAD708U manufactured by DIC Corporation; non-volatile content 40%), and 747.5 parts by weight of ion-exchanged water were stirred with a three-one motor at room temperature for 30 minutes to obtain Fiber Treatment Agent Composition B of Preparation Example B. The content of SACRAN in the fiber treatment composition B, which was determined from the blending amount, was 0.05% by mass. The content of the binder in the fiber treatment composition B was 0.1% by mass. The content of the binder was 200 parts by mass per 100 parts by mass of SACRAN. The results are shown in Table 7.
[0170] [Table 7]
[0171] "Preparation of textile products for evaluation B-1" (Reference example B1) <Attachment process> The fiber treatment composition A obtained in Preparation Example B1 was applied to a base fabric (cotton and polyester blend; M2000, manufactured by Shikibo Co., Ltd.) as a fiber substrate at a rate of 80 to 90 g / m using a mangle coater (manufactured by Tsujii Senki Kogyo Co., Ltd.). 2 The coating weight (amount of fiber treatment composition A applied per unit area of base fabric) is 0.04 to 0.05 g / m in terms of SACRAN (registered trademark) weight. 2 A base fabric having fiber treatment composition A adhered thereto was obtained.
[0172] <Drying process> The base fabric having the fiber treatment composition A applied thereto, obtained in the above application step, was subjected to a heat drying treatment at 70° C. for 1 minute to obtain a SAKRAN fiber processed product A as a processed fiber product.
[0173] (Evaluation of textile products) (1)Tactile sensation The texture of the SAKRAN fiber processed products when lightly pressed with the fingers was evaluated on the following three-level scale (ABC rank), and the results are shown in Table 7.
[0174] A: Soft and moist to the touch B: Soft or moist feel C: No softness or moist feeling
[0175] (2) Water absorption According to the JIS L-1907 Water Absorption Test Method for Textile Products (Dropping Method), a drop of water was dropped from a burette onto the textile product, and the time from when the drop reached the surface of the fiber until the drop was absorbed was measured. The average value of five textile products was rounded off to the nearest integer, and evaluated into the following three levels (ABC rank), and the results are shown in Table 7.
[0176] A: Water absorption time is 5 seconds or less B: Water absorption time is 6 to 8 seconds C: Water absorption time is 9 seconds or more
[0177] (3) Moisture absorption and release According to JIS L-1954:2022, the moisture absorption and release properties of fabrics over time test method, the mass change of the textile processed product was measured over time during the moisture absorption process in which the textile processed product was moved from the low humidity side to the high humidity side, and during the moisture release process in which the textile processed product was moved from the high humidity side to the low humidity side, and the moisture absorption rate and moisture release rate were calculated. The moisture absorption and release properties were each evaluated on the following three levels (ABC rank), and the results are shown in Table 8.
[0178] Hygroscopic A: Moisture absorption rate is 0.45% / min or more B: Moisture absorption rate is 0.40-0.44% / min. C: Moisture absorption rate is 0.39% / min or less
[0179] Moisture release A: Moisture release rate is 0.40% / min or more B: Moisture release rate is 0.35-0.39% / min. C: Moisture release rate is 0.34% / min or less
[0180] (Reference example B2) <Attachment process> A base fabric having fiber treatment composition B adhered thereto was obtained in the same manner as in Reference Example 1, except that fiber treatment composition B obtained in Preparation Example B2 was used instead of fiber treatment composition A obtained in Preparation Example B1.
[0181] <Drying process> A textile product B was produced in the same manner as in Reference Example 1, except that the textile product was dried by heating at 70° C. for 1 minute, and then further dried by heating at 130° C. for 1 minute. Evaluations were carried out in the same manner as in Reference Example 1, and the results are shown in Table 8.
[0182] (Comparative Example B1) Instead of the textile product A, a base fabric (a blend of cotton and polyester; M2000 manufactured by Shikibo Co., Ltd.) was used as it was, and evaluation was carried out in the same manner as in Reference Example 1. The results are shown in Table 8.
[0183] [Table 8]
[0184] (Consideration) As shown in Table 8, the textile products of Reference Examples 1 and 2 obtained from the textile treatment composition of the present invention were superior in terms of touch, water absorption, moisture absorption, and moisture release properties compared to the untreated textile of Comparative Example B1. It is believed that when the textile product of the present invention is used for clothing, for example, it feels good against the skin and reduces stuffiness inside the clothing.
[0185] (Evaluation of Washing Resistance of Textile Products) For the SACRAN fiber processed products C to P of Examples B1 to B11 and Comparative Examples B2 to B4, the washing resistance of the fiber processed products was evaluated by the following method. The results are shown in Tables 10, 12 and 14.
[0186] [How to evaluate washability] The washing process was carried out according to the washing conditions described in JIS L-0217-103 (JIS L 1096 G) "Symbols and methods of labeling for handling textile products." Washing test machine: A fully automatic repetitive washing machine (SAD-135E) manufactured by Tsujii Senki Kogyo Co., Ltd. was used. "Laundry liquid" The JAFET standard blend detergent available from the Japan Textile Evaluation Technology Council was used.
[0187] "Laundry process" One cycle consisted of washing and spin-drying for 5 minutes in 40°C washing liquid, followed by rinsing and spin-drying for 3 minutes in water below 30°C, and then rinsing and spin-drying for 2 minutes in water below 30°C.This washing and rinsing process was repeated 10 times.
[0188] "Evaluation of washing durability based on Sacran dyeability" The wash resistance of the textile processed products was evaluated according to the following criteria based on the degree of dyeing of the textile fabric when the Sacran remaining in the Sacran fiber processed products was dyed with Alcian blue dye before and after washing. "standard" A: Good, when the dyeing degree of the washed textile product is the same as that of the unwashed textile product. B: Somewhat effective, when the dyeing intensity of the washed textile product is slightly lighter than that of the unwashed textile product. C: No effect, when the dyeing intensity of the washed textile product is significantly lighter than that of the unwashed textile product
[0189] "Preparation of fiber treatment composition B-2" (Preparation Example B3) "Textile pretreatment composition C" According to the components of the fiber treatment composition shown in Table 9, 5.0 parts by mass of PAS (polyamine) PAS-M-1 (manufactured by Nittobo Medical Co., Ltd.) as a cationic resin, 6.0 parts by mass of SP-931 (manufactured by DIC Corporation) as a binder, and 89 parts by mass of ion-exchanged water were added, and stirred using a Three-One motor (FBL600 manufactured by HEIDON Co., Ltd.) equipped with a propeller shaft to obtain fiber pretreatment composition C of this preparation example. The results are shown in Table 9.
[0190] (Preparation example B4) "Textile pretreatment composition D" Using the components of the fiber treatment composition shown in Table 9, 8.0 parts by mass of Boncoat SFC-55 (DIC Corporation) as a cationic resin was added to 92 parts by mass of ion-exchanged water in the same manner as in Preparation Example B3, and the mixture was stirred using a Three-One motor (Heidon Corporation FBL600) equipped with a propeller shaft to obtain Fiber Pretreatment Composition D of this Preparation Example. The results are shown in Table 9.
[0191] (Preparation example B5) "Fiber treatment composition E" 995 parts by mass of ion-exchanged water was added to 5.0 parts by mass of SACRAN (Green Science Materials Co., Ltd., sulfated polysaccharide derived from Aphanothece sacrum, molecular weight: about 2 million to about 20 million) as sulfated polysaccharide, and the mixture was stirred at 75°C for 8 hours using a three-one motor (Heidon FBL600) equipped with a propeller shaft to obtain a 0.5% by mass SACRAN aqueous solution. This SACRAN aqueous solution was further diluted 2-fold with ion-exchanged water to prepare a 0.25% by mass SACRAN aqueous solution, fiber treatment composition E. The results are shown in Table 9.
[0192] [Table 9]
[0193] <Cationic resin> PAS-1: PAS (polyamine) PAS-M-1, manufactured by Nittobo Medical Co., Ltd. SFC-55: Boncoat SFC-55, manufactured by DIC Corporation <Binder> SP-931: SP-931 manufactured by DIC Corporation
[0194] "Preparation of textile products for evaluation B-2" (Examples B1 and B2) "Sakuran fiber processed products C and D" <Preparatory process: adhesion process> The fiber pretreatment compositions C and D obtained in Preparation Examples B3 and B4 above were applied to a polyester P-110 base fabric (obtained from Shikisensha Co., Ltd. as "polyester de chine", a fiber for dyeing tests) at a rate of 70 to 80 g / m using a mangle coater (manufactured by Tsujii Senki Kogyo Co., Ltd.). 2 (amount of fiber pretreatment compositions C and D applied per unit area of base fabric), calculated as the weight of the solid content in the fiber pretreatment composition, is 3 to 4 g / m 2 Thus, a base fabric having fiber pretreatment compositions C and D adhered thereto was obtained.
[0195] <Preparatory process: drying process> The base fabrics to which the fiber pretreatment compositions C and D obtained in the above-mentioned application step were applied were subjected to a heat drying treatment at 120° C. for 1 to 3 minutes. As preliminary fiber processed products, preliminary fiber processed products C and D coated with a cationic resin were obtained.
[0196] <Attachment process> The fiber treatment composition E obtained in Preparation Example B5 above was applied to a pre-processed fiber product having the fiber pretreatment compositions C and D attached thereto and coated with a cationic resin. The fiber treatment composition E was applied to the pre-processed fiber product having the fiber pretreatment compositions C and D attached thereto using a mangle coater (manufactured by Tsujii Senki Kogyo Co., Ltd.) in an amount of 70 to 80 g / m. 2 The coating weight (amount of fiber treatment composition E applied per unit area of base fabric) is 0.15 to 0.2 g / m2 in terms of SACRAN weight. 2 A base fabric was obtained with the coating weight of
[0197] <Drying process> The base fabric to which the fiber treatment composition E obtained in the above-mentioned adhesion step was attached was subjected to a heat drying treatment at 70°C for 1 minute. As the fiber processed products, fiber processed products C and D in which SACRAN was attached on the cationic resin layer were obtained. The results are shown in Table 10.
[0198] (Comparative example B2) <Attachment process> The fiber treatment composition E obtained in Preparation Example B5 was applied to a polyester P-110 base fabric (obtained from Shikisensha Co., Ltd. as "polyester de chine", a fiber for dyeing tests) as a fiber substrate using a mangle coater (manufactured by Tsujii Senki Kogyo Co., Ltd.) to obtain a base fabric to which the fiber treatment composition E was attached.
[0199] <Drying process> The base fabric having the fiber treatment composition E applied thereto, obtained in the above application step, was subjected to a heat drying treatment at 70° C. for 1 minute to obtain a SACRAN fiber processed product E as a processed fiber product.
[0200] [Table 10] TEMP: 70℃ heat treatment
[0201] "Preparation of fiber treatment composition B-3" (Preparation example B6) "Fiber treatment composition F" 995 parts by mass of ion-exchanged water was added to 5.0 parts by mass of SACRAN (Green Science Materials Co., Ltd., sulfated polysaccharide derived from Aphanothece sacrum, molecular weight: approximately 2 million to approximately 20 million) as a sulfated polysaccharide, and the mixture was stirred at 75°C for 8 hours using a Three-One Motor (Heidon FBL600) equipped with a propeller shaft to prepare a 0.5% by mass SACRAN aqueous solution. In the final composition of this Preparation Example B, a predetermined amount of the above 0.5% by mass SACRAN aqueous solution was mixed with 8 parts by mass of EPOCROS WS-500 manufactured by Nippon Shokubai Co., Ltd. as a crosslinking agent, 17 parts by mass of DEXCEL HPS PAD 602 manufactured by DIC Corporation as a binder, and 26 parts by mass of sodium carboxymethylcellulose (CMC Daicel 1350) manufactured by Daicel Miraize Co., Ltd. as a thickener, and ion-exchanged water was mixed so that the total amount of the final composition was 1000 parts by mass to obtain a fiber treatment composition F. The results are shown in Table 11.
[0202] (Preparation examples B7 to B11) Fiber treatment compositions G to K were obtained in the same manner as in Preparation Example B6 using the components of the fiber treatment compositions shown in Table 11. The results are shown in Table 11.
[0203] [Table 11]
[0204] <Crosslinking agent> WS-500: Epocross WS-500 manufactured by Nippon Shokubai Co., Ltd. XC-830: Prominate XC-830 manufactured by Aica Kogyo Co., Ltd. V-02-L2: Carbodilite V-02-L2 manufactured by Nisshinbo Chemical Co., Ltd. <Binder> HPS PAD 602: DEXCEL HPS PAD 602 manufactured by DIC Corporation <Thickener> CMC Daicel 1350: A 5% by mass aqueous solution of carboxymethylcellulose sodium / CMC Daicel 1350 manufactured by Daicel Miraize Co., Ltd. dissolved in ion-exchanged water was used.
[0205] "Preparation of textile products for evaluation B-3" (Examples B3 to B7, Comparative Example B3) <Attachment process> The fiber treatment compositions F to K obtained in Preparation Examples B6 to B11 above were placed on a 90-mesh screen stencil and coated onto a polyester P-110 base fabric (obtained from Shikisen Co., Ltd. as "polyester de chine", a fiber for dyeing tests) as a fiber substrate, to obtain a base fabric to which the fiber treatment compositions F to K were adhered.
[0206] <Drying process> The base fabrics to which the fiber treatment compositions F to K were applied, obtained in the above application step, were subjected to a heat drying treatment at 150° C. for 2 minutes. As fiber processed products, SACRAN fiber processed products F to K were obtained. The results are shown in Table 12.
[0207] [Table 12] TEMP: 150℃ heat treatment
[0208] "Preparation of fiber treatment composition 4" (Preparation example B12) "Fiber treatment composition L" 5.0 parts by mass of SACRAN (Green Science Materials Co., Ltd., sulfated polysaccharide derived from Aphanothece sacrum, molecular weight: about 2 million to about 20 million) was added to 995 parts by mass of ion-exchanged water, and the mixture was stirred at 75°C for 8 hours using a Three-One Motor (Heidon FBL600) equipped with a propeller shaft to prepare a fiber treatment composition L containing a 0.5% by mass aqueous solution of SACRAN. The results are shown in Table 13.
[0209] [Table 13]
[0210] "Preparation of textile products for evaluation B-4" (Examples B8 and B9) <Attachment process> The fiber treatment composition L obtained in Preparation Example B12 above was applied to a polyester P-110 base fabric (obtained from Shikisensha Co., Ltd. as "polyester de chine", a fiber for dyeing tests) at a rate of 70 to 80 g / m using a mangle coater (manufactured by Tsujii Senki Kogyo Co., Ltd.). 2 The coating weight (amount of fiber treatment composition C applied per unit area of base fabric) is 0.3 to 0.4 g / m2 in terms of SACRAN weight. 2 A base fabric having fiber treatment composition L adhered thereto was obtained.
[0211] <Drying process> The base fabrics to which the fiber treatment composition L was applied were subjected to heat treatment with high-temperature steam at 160° C. and 180° C. SACRAN fiber processed products L and M were obtained as processed fiber products.
[0212] (Examples B10 and B11)
[0213] <Attachment process> A base fabric having fiber treatment composition L adhered thereto was obtained in the same manner as in Example B8.
[0214] <Drying process> The base fabric having the fiber treatment composition L applied thereto, obtained in the above application step, was subjected to a heat treatment at 70° C. for 1 minute to obtain a SAKRAN fiber processed product precursor after the treatment. The SACRAN fiber processed product precursors after the above treatment were subjected to heat treatment with high-temperature steam at 160° C. and 180° C., respectively. SACRAN fiber processed products N and O were obtained as fiber processed products.
[0215] (Comparative example B4) <Attachment process> A base fabric having fiber treatment composition L adhered thereto was obtained in the same manner as in Example B10.
[0216] <Drying process> The base fabric having the fiber treatment composition L applied thereto, obtained in the above application step, was subjected to a heat drying treatment at 70° C. for 1 minute. As a fiber processed product, a SAKRAN fiber processed product P was obtained.
[0217] [Table 14]
[0218] TEMP1: Heat treatment with 160℃ high-temperature steam TEMP2: Heat treatment with 180℃ high-temperature steam TEMP3: 70℃ heat treatment + 160℃ heat treatment with high-temperature steam TEMP4: 70℃ heat treatment + 180℃ heat treatment with high-temperature steam TEMP5: 70℃ heat treatment
[0219] (Consideration) As shown in Table 10 above, by carrying out each of the treatments of Examples B1 to B2 using the fiber treatment agent of the present invention or a fiber treatment agent containing the same, it is believed that the polyester fiber SACRAN (registered trademark) fiber processed products are firmly fixed to the polyester fiber fabric base via the sulfate groups and carboxyl groups of the SACRAN molecule of the sulfated polysaccharide and the cationic resin that constitutes the fiber treatment agent.
[0220] As shown in Table 10 above, the SACRAN (registered trademark) fiber processed products using polyester fiber of Examples B1-2, which are obtained by using a fiber pretreatment agent containing the cationic resin and binder of the present invention in advance and further using a fiber treatment agent containing sulfated polysaccharides, are considered to be firmly fixed to the polyester fiber fabric of the base fabric via the sulfate group and carboxyl group of the SACRAN molecule of the sulfated polysaccharide on the surface of the fiber and the cationic resin and binder that constitute the fiber pretreatment agent. This is because the surface of the polyester fiber is charged with + (plus) electricity by the cationic resin contained in the fiber pretreatment agent, making it easier for the anionic sulfated polysaccharides having sulfate groups and carboxyl groups to approach the surface of the fiber. Furthermore, it is considered that the coexistence of the binder allows it to be firmly fixed to the surface of the fiber.
[0221] As shown in Table 12 above, in the SACRAN (registered trademark) fiber processed products having a base fabric of polyester fiber obtained by performing each of the treatments of Examples B3 to B7 using a fiber treatment agent containing the sulfated polysaccharide of the present invention, the sulfate groups and carboxyl groups of the SACRAN molecule of the sulfated polysaccharide are crosslinked with the functional groups of the crosslinking agent that constitutes the fiber treatment agent, and are further firmly fixed to the surface of the polyester fiber fabric base fabric via a binder. Furthermore, as shown in Table 14 above, the sacran molecules of sulfated polysaccharides attached to the surface of the fibers can penetrate into the interior of the polyester fibers and be firmly fixed to the polyester fibers by subjecting them to the drying and heat treatment processes of Examples B8 to B11 of the present invention. According to the present invention, the Sakuran fiber processed products shown in Examples B1 to B11 can be obtained as fibers in which the Sakuran molecules do not detach from the fibers but remain there even after repeated washing, and whose functionality such as moisture retention, moisture absorption and release, stain resistance, and antistatic properties is not impaired.
[0222] (Example C1) <Mixing> A mixture having the following composition was placed in a magnetic stirrer KS-1X (manufactured by AZONE) and stirred at 70° C. and 2000 rpm for 2 hours. Polysaccharide type: SACRAN (Green Science Materials Co., Ltd.) 0.1 parts Ion-exchanged water 99.9 parts
[0223] <Dispersion> The mixed composition after stirring and 100 parts of 0.3 mmΦ YTZ balls (manufactured by Nikkato Corporation) were placed in a plastic bottle, and the disperser was attached to a Paint Conditioner (manufactured by Toyo Seiki Co., Ltd.) and dispersed for 2 hours to obtain a dispersible fiber treatment agent, which is the mixture of Example C1.
[0224] (Comparative Example C1) In Example C1, the mixed composition obtained by carrying out only the <stirring> step before being subjected to the <dispersion> step is referred to as the fiber treatment agent of Comparative Example C1 in the present invention.
[0225] (Viscosity reduction rate in dispersible fiber treatment agent of Example C1) The viscosity of the dispersible fiber treatment agent of Example C1 after the dispersion step was measured using an E-type viscometer VISCOMETER TVE-25L (manufactured by Toki Sangyo Co., Ltd.) As a result, the viscosity of the dispersible fiber treatment agent of Example C1 after the dispersion step was 58.1 (mPa s). In Example C1, the viscosity of the mixed composition (corresponding to the fiber treatment agent of Comparative Example C1) before being subjected to the dispersion step was also measured in the same manner as in Example C1. As a result, the viscosity of the fiber treatment agent of Comparative Example C1 was 79.2 (mPa s). The viscosity reduction rate in the dispersible fiber treatment agent of Example C1 can be calculated by the following formula. [(79.2-58.1) / 79.2] x 100 The result was about 27%.
[0226] (Examples C2 to C3, Comparative Examples C2 to C3) Dispersible fiber treatment agents of Examples C2 to C3 (corresponding to Comparative Examples C2 to C3 before the dispersion process) were obtained in the same manner as Example C1, except that the content of SACRAN and the dispersion time were changed as shown in Table 15 compared to Example C1 (corresponding to Comparative Example C1 before the dispersion process). The viscosity of the dispersible fiber treatment agents in Examples C2 to C3 was measured in the same manner as in Example C1. The viscosity measurement results of the fiber treatment agents in Examples C2 to C3 and Comparative Examples C2 to C8, and the viscosity reduction rate results of the dispersible fiber treatment agents in Examples C2 to C3 are shown in Table 15.
[0227] (Examples C4 to C6) Dispersible fiber treatment agents of Examples C4 to C6 were obtained in the same manner as Examples C1 to C3 (which correspond to Comparative Examples C1 to C3 before the dispersion process), except that the content of SACRAN and the dispersion time were changed as shown in Table 15. The viscosity of the dispersible fiber treatment agents in Examples C4 to C6 was measured in the same manner as in Example C1. The viscosity measurement results of the dispersible fiber treatment agents in Examples C4 to C11 and the viscosity reduction rates of the dispersible fiber treatment agents in Examples C4 to C6 compared with Comparative Examples C1 to C3, respectively, are shown in Table 15.
[0228] (Example C7, Comparative Example C4) In the above Example C1 (which corresponds to Comparative Example C1 before the dispersion process), the agitator was changed to a Dispermat (manufactured by Eiko Seiko Co., Ltd.), the disperser was changed to a Bead Mill Labostar Mini MGF015 (manufactured by Ashizawa Finetech Co., Ltd.), the bead filling rate was set to 80%, the peripheral speed was set to 8 m / sec, and the Sacran content and dispersion time were changed as shown in Table 15. In the same manner as in Example C1, a dispersible fiber treatment agent of Example C7 (which corresponds to Comparative Example C4 before the dispersion process) was obtained. The viscosity of the dispersible fiber treatment agent in Example C7 was measured in the same manner as in Example C1. The viscosity measurement results of the fiber treatment agents in Example C7 and Comparative Example C4, and the viscosity reduction rate results of the dispersible fiber treatment agent in Example C7 are shown in Table 15.
[0229] [Table 15]
[0230] (Example C8) <Stirring> 995 parts by mass of ion-exchanged water was added to 5.0 parts by mass of SACRAN (registered trademark) (manufactured by Green Science Materials Co., Ltd., sulfated polysaccharide derived from Aphanothece sacrum, molecular weight: about 2 million to about 20 million) as sulfated polysaccharide, and the mixture was stirred at 70°C for 8.5 hours using a Three-One Motor (FBL600 manufactured by HEIDON Co., Ltd.) equipped with a propeller shaft. Furthermore, a mixed composition of 0.5% by mass of SACRAN aqueous solution was obtained using a High Flex Disper stirring device (HG92 manufactured by SMT Co., Ltd.).
[0231] <Dispersion> The previously prepared mixed composition was subjected to a bead mill dispersion process in a bead mill disperser filled with a bead mill Labstar Mini MGF015 (manufactured by Ashizawa Finetech Co., Ltd.) at a bead filling rate of 80%, at a peripheral speed of 8 m / s for 0.5 hours to produce a fiber treatment agent of 0.5 mass% SACRAN aqueous solution.
[0232] (Example C9) In the <dispersion> step of Example C8, a mixed composition obtained by carrying out a bead mill dispersion treatment for 1 hour was designated as Example C9.
[0233] (Comparative example C5) In Example C8, a mixed composition obtained by carrying out only the <stirring> step before being subjected to the <dispersion> step was used as Comparative Example C5.
[0234] (Example C10) <Stirring> Using a method similar to that used in Example C8, the sulfated polysaccharide SACRAN (registered trademark) (manufactured by Green Science Materials Co., Ltd., sulfated polysaccharide derived from Aphanothece sacrum, molecular weight: approximately 2 million to approximately 20 million) was stirred with a three-one motor at 70°C for 9 hours, and further stirred with a disperser to obtain a mixed composition of 0.5% by mass SACRAN aqueous solution.
[0235] <Dispersion> The previously prepared mixed composition was subjected to a bead mill dispersion process in a bead mill disperser filled with a bead mill Labstar Mini MGF015 (manufactured by Ashizawa Finetech Co., Ltd.) at a bead filling rate of 80% for 1.5 hours at a peripheral speed of 8 m / s to produce a fiber treatment agent in the form of a 0.5% by mass aqueous solution of SACRAN.
[0236] (Comparative example C6) In Example C10, a mixed composition obtained by carrying out only the <stirring> step before being subjected to the <dispersion> step was used as Comparative Example C6.
[0237] The viscosity values and viscosity reduction rates of the solutions of each SACRAN fiber treatment agent in Example C8 (corresponding to Comparative Example C5 before the dispersion process) and Example C10 (corresponding to Comparative Example C6 before the dispersion process) measured using the aforementioned E-type viscometer and B-type viscometer are shown in Table 16.
[0238] [Table 16]
[0239] "Preparation of fiber treatment composition" (Preparation example D1) <Stirring> 995 parts by mass of ion-exchanged water was added to 5.0 parts by mass of SACRAN (registered trademark) (manufactured by Green Science Materials Co., Ltd., sulfated polysaccharide derived from Aphanothece sacrum, molecular weight: about 2 million to about 20 million) as sulfated polysaccharide, and a 0.5% by mass SACRAN aqueous solution was prepared by stirring for 8 hours at 75 ° C. using a three-one motor (FBL600 manufactured by HEIDON Co., Ltd.) equipped with a propeller shaft. Furthermore, a mixed composition of 0.5% by mass SACRAN aqueous solution was obtained using a High Flex Disper stirring device (HG92 manufactured by SMT Co., Ltd.).
[0240] <Dispersion> The fiber treatment agent was prepared by dispersing the mixed composition prepared in advance in a bead mill disperser filled with a bead mill Labostar Mini MGF015 (manufactured by Ashizawa Finetech Co., Ltd.) at a bead filling rate of 80% at a peripheral speed of 8 m / sec for 90 minutes. A dispersible fiber treatment agent dD1 was obtained as a 0.5% by mass SACRAN aqueous solution.
[0241] In the final composition of this preparation example, dispersible fiber treatment agent dD1, a 0.5% by mass aqueous solution of SACRAN whose viscosity had been reduced by the above-mentioned stirring and dispersion treatment, Prominate XC-830 manufactured by Aica Kogyo Co., Ltd. as a crosslinking agent manufactured by Nippon Shokubai Co., Ltd., and DEXCEL HPS PAD 602 manufactured by DIC Corporation as a binder were mixed with ion-exchanged water to obtain a fiber treatment agent composition D1 with a total amount of the final composition of 1000 parts by mass. The results are shown in Table 17.
[0242] (Preparation Examples D2 to D3) Fiber treatment compositions D2 to D3 were obtained in the same manner as in Preparation Example D1, using the components of the fiber treatment compositions shown in Table 17. The results are shown in Table 17.
[0243] [Table 17]
[0244] <Crosslinking agent> XC-830: Prominate XC-830 manufactured by Aica Kogyo Co., Ltd. <Binder> HPS PAD 602: DEXCEL HPS PAD 602 manufactured by DIC Corporation
[0245] "Preparation of textile products for evaluation" (Examples D1 to D3) <Attachment process> The fiber treatment compositions D1 to D3 obtained in Preparation Examples D1 to D3 were applied to a polyester P-110 base fabric (obtained from Shikisensha Co., Ltd. as "polyester de chine", a fiber for dyeing tests) at a rate of 70 to 80 g / m using a mangle coater (manufactured by Tsujii Senki Kogyo Co., Ltd.). 2 (amount of each fiber treatment composition applied per unit area of base fabric) was applied to obtain a base fabric to which each fiber treatment composition was attached.
[0246] <Drying process 1> The base fabrics to which the fiber treatment compositions D1 and D2 were applied, obtained in the above application step, were subjected to a heat drying treatment at 150° C. for 2 minutes to obtain SACRAN fiber processed products D1 and D2.
[0247] <Drying process 2> The base fabric having the fiber treatment composition D3 applied thereto obtained in the above-mentioned application step was subjected to a heat treatment at 70° C. for 1 minute to obtain a SAKRAN fiber processed product precursor after the treatment. The SACRAN fiber processed product precursors after the above treatment were each subjected to a heat treatment with high-temperature steam at 180° C. As a fiber processed product, SACRAN fiber processed product D3 was obtained. The results are shown in Table 18.
[0248] [Table 18] TEMP6: Heat treatment at 150℃ for 2 minutes TEMP7: Heat treatment at 70℃ for 1 minute + heat treatment with high-temperature steam at 180℃
[0249] "Preparation of fiber treatment composition" (Preparation Example D4) <Stirring> 995 parts by mass of ion-exchanged water was added to 5.0 parts by mass of SACRAN (registered trademark) (manufactured by Green Science Materials Co., Ltd., sulfated polysaccharide derived from Aphanothece sacrum, molecular weight: about 2 million to about 20 million) as sulfated polysaccharide, and a 0.5% by mass SACRAN aqueous solution was prepared by stirring for 8 hours at 75 ° C. using a three-one motor (FBL600 manufactured by HEIDON Co., Ltd.) equipped with a propeller shaft. Furthermore, a mixed composition of 0.5% by mass SACRAN aqueous solution was obtained using a High Flex Disper stirring device (HG92 manufactured by SMT Co., Ltd.).
[0250] In the final composition of this preparation example, a 0.5 mass% SACRAN aqueous solution dispersion fiber treatment agent dD4 prepared by only the stirring process described above, a crosslinking agent manufactured by Nippon Shokubai Co., Ltd., a product manufactured by Aica Kogyo Co., Ltd., a product manufactured by Prominate XC-830 as a crosslinking agent, and a product manufactured by DIC Corporation, a product manufactured by DEXCEL HPS PAD 602 as a binder were mixed with ion-exchanged water so that the total amount of the final composition was 1,000 mass parts, to obtain fiber treatment agent composition D4.
[0251] "Preparation of textile products for evaluation" (Comparative Example D1) Fiber treatment composition D4 was subjected to the <application step> in the same manner as in Examples D1 to D3 described above, followed by the <drying step 3> described below, to obtain a comparative fiber product D4.
[0252] <Drying process 3> The base fabric to which the fiber treatment composition D4 was applied, obtained in the above-mentioned application step, was subjected to a heat treatment at 70° C. for 1 minute. As a comparative fiber processed product, SAKRAN fiber processed product D4 was obtained. The results are shown in Table 19.
[0253] [Table 19]
[0254] In Table 19, the meanings of the evaluation results "A, B, C" for each evaluation item are as follows: A:Very good B: Good C: Average / Average
[0255] (Comparative example D2) Instead of the textile products D1 to D4, the polyester P-110 base fabric (obtained from Shikisen Co., Ltd. as the dyeing test fiber "Polyester Decin") was used as is as the textile substrate, and evaluation was performed in the same manner as in Examples D1 to D3 and Comparative Example D1, and the results are shown in Table 20.
[0256] The evaluation items of the fabricated textile products are as follows:
[0257] [1] Washing test The washing resistance of the textile product was evaluated in the same manner as in Example B1 above. The results are shown in Table 20.
[0258] [2] Antifouling properties The stain resistance of the textile products was evaluated in the same manner as in Example A3 above. The results are shown in Table 20.
[0259] [3] Moisture absorption / release: Refer to JIS L-1954 The moisture absorption / desorption properties of the textile products were evaluated in the same manner as in Example A3 above. The results are shown in Table 20.
[0260] [4] Antistatic / antistatic properties: Method A and Method B; The moisture absorption / desorption properties of the textile products were evaluated in the same manner as in Example A3 above. The results are shown in Table 20.
[0261] [Table 20] TEMP6: Heat treatment at 150℃ for 2 minutes TEMP7: Heat treatment at 70℃ for 1 minute + heat treatment with high-temperature steam at 180℃ TEMP8: Heat treatment at 70℃ for 1 minute [Industrial Applicability]
[0262] The fiber processed product of the present embodiment is excellent in water absorption, moisture retention, moisture absorption and release properties, and is pleasant to the touch. In addition, it is also excellent in stain resistance and antistatic properties, and is therefore expected to be used in a variety of applications, including clothing such as gloves, underwear, socks, shirts, and western clothes, as well as face masks, surgical masks, materials for disposable diapers, and cosmetic sheets such as lotion wipes.
Claims
1. A fiber treatment composition comprising a fiber treatment agent and water, The fiber treatment agent contains a sulfated polysaccharide, The fiber treatment composition has a sulfated polysaccharide content of 0.001 to 5 mass %.
2. 2. The fiber treatment composition according to claim 1, wherein the sulfated polysaccharide is derived from an alga.
3. The fiber treatment composition according to claim 1 or 2, further comprising a binder.
4. The fiber treatment agent further contains water and is a dispersible fiber treatment agent obtained by a dispersion treatment, 2. The fiber treatment composition according to claim 1, wherein the dispersible fiber treatment agent has a viscosity change rate (%) of 20% or more before and after dispersion treatment, as represented by the following formula (1): [(A-B) / A]×100...(1) (In formula (1), A is the viscosity (milliPascal seconds (mPa·s)) of the fiber treatment agent before dispersion treatment, and B is the viscosity (milliPascal seconds (mPa·s)) of the dispersible fiber treatment agent after dispersion treatment.)
5. 5. The fiber treatment composition according to claim 4, wherein the content of the sulfated polysaccharide is 3.0% or less based on the total mass of the dispersible fiber treatment agent.
6. A step of mixing at least a sulfated polysaccharide and water and stirring the resulting mixed composition with a stirrer; A step of dispersing the stirred mixed composition using a disperser to obtain a dispersible fiber treatment agent; preparing a fiber treatment composition using the dispersible fiber treatment agent; A method for producing a fiber treatment composition comprising the steps of:
7. A method for producing the fiber treatment composition according to claim 4, comprising the steps of: mixing the sulfated polysaccharide with water and stirring the resulting mixed composition with a stirrer; A step of dispersing the stirred mixed composition using a disperser to obtain the dispersible fiber treatment agent; preparing a fiber treatment composition using the dispersible fiber treatment agent; A method for producing a fiber treatment composition comprising the steps of:
8. 8. The method for producing a fiber treatment composition according to claim 6 or 7, wherein the stirrer is at least one selected from the group consisting of a homodisper, an emulsifier, a line mixer, a three-one motor, and a magnetic stirrer.
9. 8. The method for producing a fiber treatment composition according to claim 6 or 7, wherein the dispersing machine is at least one selected from the group consisting of a sand mill, a bead mill, a pebble mill, a ball mill, a pearl mill, a basket mill, an attritor, a Dyno Mill, a bore mill, a Viscomill, a motor mill, an SC mill, a drys mill, a paint conditioner, an ultrasonic dispersing machine (ultrasonic homogenizer), a high-pressure homogenizer, a Nanomizer, an Ultimizer, a roll mill, a Henschel mixer, a pressure kneader, an intensive mixer, a Banbury mixer, and a planetary mixer.
10. A textile processed product comprising a textile substrate and a textile treatment agent adhered to the textile substrate, The fiber treatment agent is contained in the fiber treatment agent composition according to claim 1 or 4, The fiber base material does not contain rayon, The amount of the sulfated polysaccharide attached to the fiber base material is 0.003 to 20.0 parts by mass per 100 parts by mass of the fiber base material.
11. A method for producing a textile product, comprising a step of treating a textile substrate with the textile treatment composition according to claim 1 or 4 to obtain a textile product, A method for producing a textile product, comprising: an application step of applying the fiber treatment composition to the textile substrate; and a drying step of removing water from the textile substrate to which the fiber treatment composition has been applied.
12. A method for producing a textile product, comprising a step of treating a textile substrate with the textile treatment composition according to claim 1 or 4 to obtain a textile product, The manufacturing method includes a step of applying the fiber treatment composition to the fiber substrate, and a step of drying the fiber substrate to remove water from the fiber substrate to which the fiber treatment composition has been applied, A method for producing a textile product, characterized in that the method is at least one selected from the group consisting of the following (I) to (III): (I) before the adhesion step, a step of pretreating a fiber substrate with a fiber pretreatment composition containing a cationic resin to obtain a pretreated fiber substrate, The applying step is a step of applying the fiber treatment composition to the pre-treated fiber substrate. (II) The fiber treatment composition further contains a crosslinking agent, and the drying step includes a heat treatment step at a temperature in the range of 80°C to 260°C. (III) The drying step includes a heat treatment step using high-temperature steam at a temperature range of 120° C. or higher.
13. A textile product manufactured by using the method for manufacturing a textile product according to claim 12, The amount of the sulfated polysaccharide attached to the fiber base material is 0.003 to 20.0 parts by mass per 100 parts by mass of the fiber base material.
Citation Information
Patent Citations
Rayon fiber
JP2019011542A